Liouville principles and a large-scale regularity theory for random elliptic operators on the half-space - Fischer, Julian L; Raithel, Claudia (SIAM Journal on Mathematical Analysis)
We consider the large-scale regularity of solutions to second-order linear elliptic equations with random coefficient fields. In contrast to previous works on regularity theory for random elliptic operators, our interest is in the regularity at the boundary: We consider problems posed on the half-space with homogeneous Dirichlet boundary conditions and derive an associated C1,α-type large-scale regularity theory in the form of a corresponding decay estimate for the homogenization-adapted tilt-excess. This regularity theory entails an associated Liouville-type theorem. The results are based on the existence of homogenization correctors adapted to the half-space setting, which we construct-by an entirely deterministic argument-as a modification of the homogenization corrector on the whole space. This adaption procedure is carried out inductively on larger scales, crucially relying on the regularity theory already established on smaller scales.

Data from: X-linkage is not a general inhibitor of tissue-specific gene expression in Drosophila melanogaster - Argyridou, Eliza; Huylmans, Ann K; Königer, Annabella; Parsch, John
As a consequence of its difference in copy number between males and females, the X chromosome is subject to unique evolutionary forces and gene regulatory mechanisms. Previous studies of Drosophila melanogaster have shown that the expression of X-linked, testis-specific reporter genes is suppressed in the male germline. However, it is not known whether this phenomenon is restricted to testis-expressed genes or if it is a more general property of genes with tissue-specific expression, which are also underrepresented on the X chromosome. To test this, we compared the expression of three tissue-specific reporter genes (ovary, accessory gland and Malpighian tubule) inserted at various autosomal and X-chromosomal locations. In contrast to testis-specific reporter genes, we found no reduction of X-linked expression in any of the other tissues. In accessory gland and Malpighian tubule, we detected higher expression of the X-linked reporter genes, which suggests that they are at least partially dosage compensated. We found no difference in the tissue-specificity of X-linked and autosomal reporter genes. These findings indicate that, in general, the X chromosome is not a detrimental environment for tissue-specific gene expression and that the suppression of X-linked expression is limited to the male germline.

Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae - Greenwood, Jenny; Milutinovic, Barbara; Peuß, Robert; Behrens, Sarah; Essar, Daniela; Rosenstiel, Philip; Schulenburg, Hinrich; Kurtz, Joachim (BMC Genomics)
Background: The phenomenon of immune priming, i.e. enhanced protection following a secondary exposure to a pathogen, has now been demonstrated in a wide range of invertebrate species. Despite accumulating phenotypic evidence, knowledge of its mechanistic underpinnings is currently very limited. Here we used the system of the red flour beetle, Tribolium castaneum and the insect pathogen Bacillus thuringiensis (Bt) to further our molecular understanding of the oral immune priming phenomenon. We addressed how ingestion of bacterial cues (derived from spore supernatants) of an orally pathogenic and non-pathogenic Bt strain affects gene expression upon later challenge exposure, using a whole-transcriptome sequencing approach. Results: Whereas gene expression of individuals primed with the orally non-pathogenic strain showed minor changes to controls, we found that priming with the pathogenic strain induced regulation of a large set of distinct genes, many of which are known immune candidates. Intriguingly, the immune repertoire activated upon priming and subsequent challenge qualitatively differed from the one mounted upon infection with Bt without previous priming. Moreover, a large subset of priming-specific genes showed an inverse regulation compared to their regulation upon challenge only. Conclusions: Our data demonstrate that gene expression upon infection is strongly affected by previous immune priming. We hypothesise that this shift in gene expression indicates activation of a more targeted and efficient response towards a previously encountered pathogen, in anticipation of potential secondary encounter.

Faster algorithms for weighted recursive state machines - Chatterjee, Krishnendu; Kragl, Bernhard; Mishra, Samarth; Pavlogiannis, Andreas
Pushdown systems (PDSs) and recursive state machines (RSMs), which are linearly equivalent, are standard models for interprocedural analysis. Yet RSMs are more convenient as they (a) explicitly model function calls and returns, and (b) specify many natural parameters for algorithmic analysis, e.g., the number of entries and exits. We consider a general framework where RSM transitions are labeled from a semiring and path properties are algebraic with semiring operations, which can model, e.g., interprocedural reachability and dataflow analysis problems. Our main contributions are new algorithms for several fundamental problems. As compared to a direct translation of RSMs to PDSs and the best-known existing bounds of PDSs, our analysis algorithm improves the complexity for finite-height semirings (that subsumes reachability and standard dataflow properties). We further consider the problem of extracting distance values from the representation structures computed by our algorithm, and give efficient algorithms that distinguish the complexity of a one-time preprocessing from the complexity of each individual query. Another advantage of our algorithm is that our improvements carry over to the concurrent setting, where we improve the bestknown complexity for the context-bounded analysis of concurrent RSMs. Finally, we provide a prototype implementation that gives a significant speed-up on several benchmarks from the SLAM/SDV project.

Spatiotemporal mechanisms of root branching - Ötvös, Krisztina; Benková, Eva (Current Opinion in Genetics & Development)
The fundamental tasks of the root system are, besides anchoring, mediating interactions between plant and soil and providing the plant with water and nutrients. The architecture of the root system is controlled by endogenous mechanisms that constantly integrate environmental signals, such as availability of nutrients and water. Extremely important for efficient soil exploitation and survival under less favorable conditions is the developmental flexibility of the root system that is largely determined by its postembryonic branching capacity. Modulation of initiation and outgrowth of lateral roots provides roots with an exceptional plasticity, allows optimal adjustment to underground heterogeneity, and enables effective soil exploitation and use of resources. Here we discuss recent advances in understanding the molecular mechanisms that shape the plant root system and integrate external cues to adapt to the changing environment.

Local law for random Gram matrices - Alt, Johannes; Erdös, László; Krüger, Torben H (Electronic Journal of Probability)
We prove a local law in the bulk of the spectrum for random Gram matrices XX∗, a generalization of sample covariance matrices, where X is a large matrix with independent, centered entries with arbitrary variances. The limiting eigenvalue density that generalizes the Marchenko-Pastur law is determined by solving a system of nonlinear equations. Our entrywise and averaged local laws are on the optimal scale with the optimal error bounds. They hold both in the square case (hard edge) and in the properly rectangular case (soft edge). In the latter case we also establish a macroscopic gap away from zero in the spectrum of XX∗.

Optimizing expectation with guarantees in POMDPs - Chatterjee, Krishnendu; Novotny, Petr; Pérez, Guillermo; Raskin, Jean; Zikelic, Djordje (Proceedings of the 31st AAAI Conference on Artificial Intelligence)
A standard objective in partially-observable Markov decision processes (POMDPs) is to find a policy that maximizes the expected discounted-sum payoff. However, such policies may still permit unlikely but highly undesirable outcomes, which is problematic especially in safety-critical applications. Recently, there has been a surge of interest in POMDPs where the goal is to maximize the probability to ensure that the payoff is at least a given threshold, but these approaches do not consider any optimization beyond satisfying this threshold constraint. In this work we go beyond both the “expectation” and “threshold” approaches and consider a “guaranteed payoff optimization (GPO)” problem for POMDPs, where we are given a threshold t and the objective is to find a policy σ such that a) each possible outcome of σ yields a discounted-sum payoff of at least t, and b) the expected discounted-sum payoff of σ is optimal (or near-optimal) among all policies satisfying a). We present a practical approach to tackle the GPO problem and evaluate it on standard POMDP benchmarks.

Additional file 1: Table S1. of Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae - Greenwood, Jenny; Milutinovic, Barbara; Peuß, Robert; Behrens, Sarah; Essar, Daniela; Rosenstiel, Philip; Schulenburg, Hinrich; Kurtz, Joachim
Lists of all differentially expressed genes in the different priming-challenge treatments (compared to the fully naïve control; xlsx file). Relevant columns include the following: sample_1 and sample_2 – treatment groups being compared; Normalised FPKM sample_1 and sample_2 – FPKM of samples being compared; log2(fold_change) – log2(FPKM sample 2/FPKM sample 1), i.e. negative means sample 1 upregulated compared with sample 2, positive means sample 2 upregulated compared with sample 1; cuffdiff test_statistic – test statistic of differential expression test; p_value – p-value of differential expression test; q_value (FDR correction) – adjusted P-value of differential expression test. (XLSX 598 kb)

Additional file 5: Table S3. of Oral immune priming with Bacillus thuringiensis induces a shift in the gene expression of Tribolium castaneum larvae - Greenwood, Jenny; Milutinovic, Barbara; Peuß, Robert; Behrens, Sarah; Essar, Daniela; Rosenstiel, Philip; Schulenburg, Hinrich; Kurtz, Joachim

Functionality-aware retargeting of mechanisms to 3D shapes - Zhang, Ran; Auzinger, Thomas; Ceylan, Duygu; Li, Wilmot; Bickel, Bernd
We present an interactive design system to create functional mechanical objects. Our computational approach allows novice users to retarget an existing mechanical template to a user-specified input shape. Our proposed representation for a mechanical template encodes a parameterized mechanism, mechanical constraints that ensure a physically valid configuration, spatial relationships of mechanical parts to the user-provided shape, and functional constraints that specify an intended functionality. We provide an intuitive interface and optimization-in-the-loop approach for finding a valid configuration of the mechanism and the shape to ensure that higher-level functional goals are met. Our algorithm interactively optimizes the mechanism while the user manipulates the placement of mechanical components and the shape. Our system allows users to efficiently explore various design choices and to synthesize customized mechanical objects that can be fabricated with rapid prototyping technologies. We demonstrate the efficacy of our approach by retargeting various mechanical templates to different shapes and fabricating the resulting functional mechanical objects.

CurveUps: Shaping objects from flat plates with tension-actuated curvature - Guseinov, Ruslan; Miguel, Eder; Bickel, Bernd
We present a computational approach for designing CurveUps, curvy shells that form from an initially flat state. They consist of small rigid tiles that are tightly held together by two pre-stretched elastic sheets attached to them. Our method allows the realization of smooth, doubly curved surfaces that can be fabricated as a flat piece. Once released, the restoring forces of the pre-stretched sheets support the object to take shape in 3D. CurveUps are structurally stable in their target configuration. The design process starts with a target surface. Our method generates a tile layout in 2D and optimizes the distribution, shape, and attachment areas of the tiles to obtain a configuration that is fabricable and in which the curved up state closely matches the target. Our approach is based on an efficient approximate model and a local optimization strategy for an otherwise intractable nonlinear optimization problem. We demonstrate the effectiveness of our approach for a wide range of shapes, all realized as physical prototypes.

An abstraction-refinement methodology for reasoning about network games - Avni, Guy; Guha, Shibashis; Kupferman, Orna
Network games (NGs) are played on directed graphs and are extensively used in network design and analysis. Search problems for NGs include finding special strategy profiles such as a Nash equilibrium and a globally optimal solution. The networks modeled by NGs may be huge. In formal verification, abstraction has proven to be an extremely effective technique for reasoning about systems with big and even infinite state spaces. We describe an abstraction-refinement methodology for reasoning about NGs. Our methodology is based on an abstraction function that maps the state space of an NG to a much smaller state space. We search for a global optimum and a Nash equilibrium by reasoning on an under- and an overapproximation defined on top of this smaller state space. When the approximations are too coarse to find such profiles, we refine the abstraction function. Our experimental results demonstrate the efficiency of the methodology.

PixelCNN models with auxiliary variables for natural image modeling - Kolesnikov, Alexander; Lampert, Christoph (34th International Conference on Machine Learning)
We study probabilistic models of natural images and extend the autoregressive family of PixelCNN models by incorporating latent variables. Subsequently, we describe two new generative image models that exploit different image transformations as latent variables: a quantized grayscale view of the image or a multi-resolution image pyramid. The proposed models tackle two known shortcomings of existing PixelCNN models: 1) their tendency to focus on low-level image details, while largely ignoring high-level image information, such as object shapes, and 2) their computationally costly procedure for image sampling. We experimentally demonstrate benefits of our LatentPixelCNN models, in particular showing that they produce much more realistically looking image samples than previous state-of-the-art probabilistic models.

iCaRL: Incremental classifier and representation learning - Rebuffi, Sylvestre Alvise; Kolesnikov, Alexander; Sperl, Georg; Lampert, Christoph
A major open problem on the road to artificial intelligence is the development of incrementally learning systems that learn about more and more concepts over time from a stream of data. In this work, we introduce a new training strategy, iCaRL, that allows learning in such a class-incremental way: only the training data for a small number of classes has to be present at the same time and new classes can be added progressively. iCaRL learns strong classifiers and a data representation simultaneously. This distinguishes it from earlier works that were fundamentally limited to fixed data representations and therefore incompatible with deep learning architectures. We show by experiments on CIFAR-100 and ImageNet ILSVRC 2012 data that iCaRL can learn many classes incrementally over a long period of time where other strategies quickly fail.

Divergence and evolution of assortative mating in a polygenic trait model of speciation with gene flow - Sachdeva, Himani; Barton, Nicholas H (Evolution; International Journal of Organic Evolution)
Assortative mating is an important driver of speciation in populations with gene flow and is predicted to evolve under certain conditions in few-locus models. However, the evolution of assortment is less understood for mating based on quantitative traits, which are often characterized by high genetic variability and extensive linkage disequilibrium between trait loci. We explore this scenario for a two-deme model with migration, by considering a single polygenic trait subject to divergent viability selection across demes, as well as assortative mating and sexual selection within demes, and investigate how trait divergence is shaped by various evolutionary forces. Our analysis reveals the existence of sharp thresholds of assortment strength, at which divergence increases dramatically. We also study the evolution of assortment via invasion of modifiers of mate discrimination and show that the ES assortment strength has an intermediate value under a range of migration-selection parameters, even in diverged populations, due to subtle effects which depend sensitively on the extent of phenotypic variation within these populations. The evolutionary dynamics of the polygenic trait is studied using the hypergeometric and infinitesimal models. We further investigate the sensitivity of our results to the assumptions of the hypergeometric model, using individual-based simulations.

Current-phase relation of ballistic graphene Josephson junctions - Nanda, Gaurav; Aguilera Servin, Juan L; Rakyta, Péter; Kormányos, Andor; Kleiner, Reinhold; Koelle, Dieter; Watanabe, Kazuo; Taniguchi, Takashi; Vandersypen, Lieven; Goswami, Srijit (Nano Letters)
The current-phase relation (CPR) of a Josephson junction (JJ) determines how the supercurrent evolves with the superconducting phase difference across the junction. Knowledge of the CPR is essential in order to understand the response of a JJ to various external parameters. Despite the rising interest in ultraclean encapsulated graphene JJs, the CPR of such junctions remains unknown. Here, we use a fully gate-tunable graphene superconducting quantum intereference device (SQUID) to determine the CPR of ballistic graphene JJs. Each of the two JJs in the SQUID is made with graphene encapsulated in hexagonal boron nitride. By independently controlling the critical current of the JJs, we can operate the SQUID either in a symmetric or asymmetric configuration. The highly asymmetric SQUID allows us to phase-bias one of the JJs and thereby directly obtain its CPR. The CPR is found to be skewed, deviating significantly from a sinusoidal form. The skewness can be tuned with the gate voltage and oscillates in antiphase with Fabry-Pérot resistance oscillations of the ballistic graphene cavity. We compare our experiments with tight-binding calculations that include realistic graphene-superconductor interfaces and find a good qualitative agreement.

Subsampling scaling - Levina (Martius), Anna; Priesemann, Viola (Nature Communications)
In real-world applications, observations are often constrained to a small fraction of a system. Such spatial subsampling can be caused by the inaccessibility or the sheer size of the system, and cannot be overcome by longer sampling. Spatial subsampling can strongly bias inferences about a system’s aggregated properties. To overcome the bias, we derive analytically a subsampling scaling framework that is applicable to different observables, including distributions of neuronal avalanches, of number of people infected during an epidemic outbreak, and of node degrees. We demonstrate how to infer the correct distributions of the underlying full system, how to apply it to distinguish critical from subcritical systems, and how to disentangle subsampling and finite size effects. Lastly, we apply subsampling scaling to neuronal avalanche models and to recordings from developing neural networks. We show that only mature, but not young networks follow power-law scaling, indicating self-organization to criticality during development.

Diagrammatic approach to orbital quantum impurities interacting with a many-particle environment - Bighin, Giacomo; Lemeshko, Mikhail (Physical Review B - Condensed Matter and Materials Physics)
Recently it was shown that an impurity exchanging orbital angular momentum with a surrounding bath can be described in terms of the angulon quasiparticle [Phys. Rev. Lett. 118, 095301 (2017)]. The angulon consists of a quantum rotor dressed by a many-particle field of boson excitations, and can be formed out of, for example, a molecule or a nonspherical atom in superfluid helium, or out of an electron coupled to lattice phonons or a Bose condensate. Here we develop an approach to the angulon based on the path-integral formalism, which sets the ground for a systematic, perturbative treatment of the angulon problem. The resulting perturbation series can be interpreted in terms of Feynman diagrams, from which, in turn, one can derive a set of diagrammatic rules. These rules extend the machinery of the graphical theory of angular momentum - well known from theoretical atomic spectroscopy - to the case where an environment with an infinite number of degrees of freedom is present. In particular, we show that each diagram can be interpreted as a 'skeleton', which enforces angular momentum conservation, dressed by an additional many-body contribution. This connection between the angulon theory and the graphical theory of angular momentum is particularly important as it allows to systematically and substantially simplify the analytical representation of each diagram. In order to exemplify the technique, we calculate the 1- and 2-loop contributions to the angulon self-energy, the spectral function, and the quasiparticle weight. The diagrammatic theory we develop paves the way to investigate next-to-leading order quantities in a more compact way compared to the variational approaches.

Transport based image morphing with intensity modulation - Maas, Jan; Rumpf, Martin; Simon, Stefan
We present a generalized optimal transport model in which the mass-preserving constraint for the L2-Wasserstein distance is relaxed by introducing a source term in the continuity equation. The source term is also incorporated in the path energy by means of its squared L2-norm in time of a functional with linear growth in space. This extension of the original transport model enables local density modulations, which is a desirable feature in applications such as image warping and blending. A key advantage of the use of a functional with linear growth in space is that it allows for singular sources and sinks, which can be supported on points or lines. On a technical level, the L2-norm in time ensures a disintegration of the source in time, which we use to obtain the well-posedness of the model and the existence of geodesic paths. The numerical discretization is based on the proximal splitting approach [18] and selected numerical test cases show the potential of the proposed approach. Furthermore, the approach is applied to the warping and blending of textures.

Fingerprints of angulon instabilities in the spectra of matrix-isolated molecules - Cherepanov, Igor; Lemeshko, Mikhail (Physical Review Materials)
The formation of vortices is usually considered to be the main mechanism of angular momentum disposal in superfluids. Recently, it was predicted that a superfluid can acquire angular momentum via an alternative, microscopic route -- namely, through interaction with rotating impurities, forming so-called `angulon quasiparticles' [Phys. Rev. Lett. 114, 203001 (2015)]. The angulon instabilities correspond to transfer of a small number of angular momentum quanta from the impurity to the superfluid, as opposed to vortex instabilities, where angular momentum is quantized in units of ℏ per atom. Furthermore, since conventional impurities (such as molecules) represent three-dimensional (3D) rotors, the angular momentum transferred is intrinsically 3D as well, as opposed to a merely planar rotation which is inherent to vortices. Herein we show that the angulon theory can explain the anomalous broadening of the spectroscopic lines observed for CH 3 and NH 3 molecules in superfluid helium nanodroplets, thereby providing a fingerprint of the emerging angulon instabilities in experiment.

Synaptotagmins: That’s why so many - Chen, Chong; Jonas, Peter M (Neuron)
Synaptotagmin 7 (Syt7) was originally identified as a slow Ca2+ sensor for lysosome fusion, but its function at fast synapses is controversial. The paper by Luo and Südhof (2017) in this issue of Neuron shows that at the calyx of Held in the auditory brainstem Syt7 triggers asynchronous release during stimulus trains, resulting in reliable and temporally precise high-frequency transmission. Thus, a slow Ca2+ sensor contributes to the fast signaling properties of the calyx synapse.

On the mechanistic nature of epistasis in a canonical cis-regulatory element - Lagator, Mato; Paixao, Tiago; Barton, Nicholas H; Bollback, Jonathan P; Guet, Calin C (eLife)
Understanding the relation between genotype and phenotype remains a major challenge. The difficulty of predicting individual mutation effects, and particularly the interactions between them, has prevented the development of a comprehensive theory that links genotypic changes to their phenotypic effects. We show that a general thermodynamic framework for gene regulation, based on a biophysical understanding of protein-DNA binding, accurately predicts the sign of epistasis in a canonical cis-regulatory element consisting of overlapping RNA polymerase and repressor binding sites. Sign and magnitude of individual mutation effects are sufficient to predict the sign of epistasis and its environmental dependence. Thus, the thermodynamic model offers the correct null prediction for epistasis between mutations across DNA-binding sites. Our results indicate that a predictive theory for the effects of cis-regulatory mutations is possible from first principles, as long as the essential molecular mechanisms and the constraints these impose on a biological system are accounted for.

Evolution of new regulatory functions on biophysically realistic fitness landscapes - Friedlander, Tamar; Prizak, Roshan; Barton, Nicholas H; Tkacik, Gasper (Nature Communications)
Gene expression is controlled by networks of regulatory proteins that interact specifically with external signals and DNA regulatory sequences. These interactions force the network components to co-evolve so as to continually maintain function. Yet, existing models of evolution mostly focus on isolated genetic elements. In contrast, we study the essential process by which regulatory networks grow: the duplication and subsequent specialization of network components. We synthesize a biophysical model of molecular interactions with the evolutionary framework to find the conditions and pathways by which new regulatory functions emerge. We show that specialization of new network components is usually slow, but can be drastically accelerated in the presence of regulatory crosstalk and mutations that promote promiscuous interactions between network components.

Model counting for recursively-defined strings - Trinh, Minh; Chu, Duc Hiep; Jaffar, Joxan
We present a new algorithm for model counting of a class of string constraints. In addition to the classic operation of concatenation, our class includes some recursively defined operations such as Kleene closure, and replacement of substrings. Additionally, our class also includes length constraints on the string expressions, which means, by requiring reasoning about numbers, that we face a multi-sorted logic. In the end, our string constraints are motivated by their use in programming for web applications. Our algorithm comprises two novel features: the ability to use a technique of (1) partial derivatives for constraints that are already in a solved form, i.e. a form where its (string) satisfiability is clearly displayed, and (2) non-progression, where cyclic reasoning in the reduction process may be terminated (thus allowing for the algorithm to look elsewhere). Finally, we experimentally compare our model counter with two recent works on model counting of similar constraints, SMC [18] and ABC [5], to demonstrate its superior performance.

The sources of adaptive evolution - Charlesworth, Deborah; Barton, Nicholas H; Charlesworth, Brian (Proceedings of the Royal Society of London Series B Biological Sciences)
The role of natural selection in the evolution of adaptive phenotypes has undergone constant probing by evolutionary biologists, employing both theoretical and empirical approaches. As Darwin noted, natural selection can act together with other processes, including random changes in the frequencies of phenotypic differences that are not under strong selection, and changes in the environment, which may reflect evolutionary changes in the organisms themselves. As understanding of genetics developed after 1900, the new genetic discoveries were incorporated into evolutionary biology. The resulting general principles were summarized by Julian Huxley in his 1942 book Evolution: the modern synthesis. Here, we examine how recent advances in genetics, developmental biology and molecular biology, including epigenetics, relate to today's understanding of the evolution of adaptations. We illustrate how careful genetic studies have repeatedly shown that apparently puzzling results in a wide diversity of organisms involve processes that are consistent with neo-Darwinism. They do not support important roles in adaptation for processes such as directed mutation or the inheritance of acquired characters, and therefore no radical revision of our understanding of the mechanism of adaptive evolution is needed.

Scales and multimodal flux distributions in stationary metabolic network models via thermodynamics - De Martino, Daniele (Physical Review E Statistical Nonlinear and Soft Matter Physics)
In this work it is shown that scale-free tails in metabolic flux distributions inferred in stationary models are an artifact due to reactions involved in thermodynamically unfeasible cycles, unbounded by physical constraints and in principle able to perform work without expenditure of free energy. After implementing thermodynamic constraints by removing such loops, metabolic flux distributions scale meaningfully with the physical limiting factors, acquiring in turn a richer multimodal structure potentially leading to symmetry breaking while optimizing for objective functions.

Gradient flow and entropy inequalities for quantum Markov semigroups with detailed balance - Carlen, Eric; Maas, Jan (Journal of Functional Analysis)
We study a class of ergodic quantum Markov semigroups on finite-dimensional unital C⁎-algebras. These semigroups have a unique stationary state σ, and we are concerned with those that satisfy a quantum detailed balance condition with respect to σ. We show that the evolution on the set of states that is given by such a quantum Markov semigroup is gradient flow for the relative entropy with respect to σ in a particular Riemannian metric on the set of states. This metric is a non-commutative analog of the 2-Wasserstein metric, and in several interesting cases we are able to show, in analogy with work of Otto on gradient flows with respect to the classical 2-Wasserstein metric, that the relative entropy is strictly and uniformly convex with respect to the Riemannian metric introduced here. As a consequence, we obtain a number of new inequalities for the decay of relative entropy for ergodic quantum Markov semigroups with detailed balance.

Deploying dengue-suppressing Wolbachia: Robust models predict slow but effective spatial spread in Aedes aegypti - Turelli, Michael; Barton, Nicholas H (Theoretical Population Biology)
A novel strategy for controlling the spread of arboviral diseases such as dengue, Zika and chikungunya is to transform mosquito populations with virus-suppressing Wolbachia. In general, Wolbachia transinfected into mosquitoes induce fitness costs through lower viability or fecundity. These maternally inherited bacteria also produce a frequency-dependent advantage for infected females by inducing cytoplasmic incompatibility (CI), which kills the embryos produced by uninfected females mated to infected males. These competing effects, a frequency-dependent advantage and frequency-independent costs, produce bistable Wolbachia frequency dynamics. Above a threshold frequency, denoted pˆ, CI drives fitness-decreasing Wolbachia transinfections through local populations; but below pˆ, infection frequencies tend to decline to zero. If pˆ is not too high, CI also drives spatial spread once infections become established over sufficiently large areas. We illustrate how simple models provide testable predictions concerning the spatial and temporal dynamics of Wolbachia introductions, focusing on rate of spatial spread, the shape of spreading waves, and the conditions for initiating spread from local introductions. First, we consider the robustness of diffusion-based predictions to incorporating two important features of wMel-Aedes aegypti biology that may be inconsistent with the diffusion approximations, namely fast local dynamics induced by complete CI (i.e., all embryos produced from incompatible crosses die) and long-tailed, non-Gaussian dispersal. With complete CI, our numerical analyses show that long-tailed dispersal changes wave-width predictions only slightly; but it can significantly reduce wave speed relative to the diffusion prediction; it also allows smaller local introductions to initiate spatial spread. Second, we use approximations for pˆ and dispersal distances to predict the outcome of 2013 releases of wMel-infected Aedes aegypti in Cairns, Australia, Third, we describe new data from Ae. aegypti populations near Cairns, Australia that demonstrate long-distance dispersal and provide an approximate lower bound on pˆ for wMel in northeastern Australia. Finally, we apply our analyses to produce operational guidelines for efficient transformation of vector populations over large areas. We demonstrate that even very slow spatial spread, on the order of 10-20 m/month (as predicted), can produce area-wide population transformation within a few years following initial releases covering about 20-30% of the target area.

Local introduction and heterogeneous spatial spread of dengue-suppressing Wolbachia through an urban population of Aedes Aegypti - Schmidt, Tom; Barton, Nicholas H; Rasic, Gordana; Turley, Andrew; Montgomery, Brian; Iturbe Ormaetxe, Inaki; Cook, Peter; Ryan, Peter; Ritchie, Scott; Hoffmann, Ary; O’Neill, Scott; Turelli, Michael (PLoS Biology)
Dengue-suppressing Wolbachia strains are promising tools for arbovirus control, particularly as they have the potential to self-spread following local introductions. To test this, we followed the frequency of the transinfected Wolbachia strain wMel through Ae. aegypti in Cairns, Australia, following releases at 3 nonisolated locations within the city in early 2013. Spatial spread was analysed graphically using interpolation and by fitting a statistical model describing the position and width of the wave. For the larger 2 of the 3 releases (covering 0.97 km2 and 0.52 km2), we observed slow but steady spatial spread, at about 100–200 m per year, roughly consistent with theoretical predictions. In contrast, the smallest release (0.11 km2) produced erratic temporal and spatial dynamics, with little evidence of spread after 2 years. This is consistent with the prediction concerning fitness-decreasing Wolbachia transinfections that a minimum release area is needed to achieve stable local establishment and spread in continuous habitats. Our graphical and likelihood analyses produced broadly consistent estimates of wave speed and wave width. Spread at all sites was spatially heterogeneous, suggesting that environmental heterogeneity will affect large-scale Wolbachia transformations of urban mosquito populations. The persistence and spread of Wolbachia in release areas meeting minimum area requirements indicates the promise of successful large-scale population transfo

Quantifying the entropic cost of cellular growth control - De Martino, Daniele; Capuani, Fabrizio; De Martino, Andrea (Physical Review E Statistical Nonlinear and Soft Matter Physics)
Viewing the ways a living cell can organize its metabolism as the phase space of a physical system, regulation can be seen as the ability to reduce the entropy of that space by selecting specific cellular configurations that are, in some sense, optimal. Here we quantify the amount of regulation required to control a cell's growth rate by a maximum-entropy approach to the space of underlying metabolic phenotypes, where a configuration corresponds to a metabolic flux pattern as described by genome-scale models. We link the mean growth rate achieved by a population of cells to the minimal amount of metabolic regulation needed to achieve it through a phase diagram that highlights how growth suppression can be as costly (in regulatory terms) as growth enhancement. Moreover, we provide an interpretation of the inverse temperature β controlling maximum-entropy distributions based on the underlying growth dynamics. Specifically, we show that the asymptotic value of β for a cell population can be expected to depend on (i) the carrying capacity of the environment, (ii) the initial size of the colony, and (iii) the probability distribution from which the inoculum was sampled. Results obtained for E. coli and human cells are found to be remarkably consistent with empirical evidence.

Excel file with data on mosquito densities, Wolbachia infection status and housing characteristics - Schmidt, Tom; Barton, Nicholas H; Rasic, Gordana; Turley, Andrew; Montgomery, Brian; Iturbe Ormaetxe, Inaki; Cook, Peter; Ryan, Peter; Ritchie, Scott; Hoffmann, Ary; O’Neill, Scott; Turelli, Michael

Supporting information concerning observed wMel frequencies and analyses of habitat variables - Schmidt, Tom; Barton, Nicholas H; Rasic, Gordana; Turley, Andrew; Montgomery, Brian; Iturbe Ormaetxe, Inaki; Cook, Peter; Ryan, Peter; Ritchie, Scott; Hoffmann, Ary; O’Neill, Scott; Turelli, Michael

Supporting Information concerning additional likelihood analyses and results - Schmidt, Tom; Barton, Nicholas H; Rasic, Gordana; Turley, Andrew; Montgomery, Brian; Iturbe Ormaetxe, Inaki; Cook, Peter; Ryan, Peter; Ritchie, Scott; Hoffmann, Ary; O’Neill, Scott; Turelli, Michael

Global dosage compensation is ubiquitous in Lepidoptera, but counteracted by the masculinization of the Z chromosome - Huylmans, Ann K; Macon, Ariana; Vicoso, Beatriz (Molecular Biology and Evolution)
While chromosome-wide dosage compensation of the X chromosome has been found in many species, studies in ZW clades have indicated that compensation of the Z is more localized and/or incomplete. In the ZW Lepidoptera, some species show complete compensation of the Z chromosome, while others lack full equalization, but what drives these inconsistencies is unclear. Here, we compare patterns of male and female gene expression on the Z chromosome of two closely related butterfly species, Papilio xuthus and Papilio machaon, and in multiple tissues of two moths species, Plodia interpunctella and Bombyx mori, which were previously found to differ in the extent to which they equalize Z-linked gene expression between the sexes. We find that, while some species and tissues seem to have incomplete dosage compensation, this is in fact due to the accumulation of male-biased genes and the depletion of female-biased genes on the Z chromosome. Once this is accounted for, the Z chromosome is fully compensated in all four species, through the up-regulation of Z expression in females and in some cases additional down-regulation in males. We further find that both sex-biased genes and Z-linked genes have increased rates of expression divergence in this clade, and that this can lead to fast shifts in patterns of gene expression even between closely related species. Taken together, these results show that the uneven distribution of sex-biased genes on sex chromosomes can confound conclusions about dosage compensation and that Z chromosome-wide dosage compensation is not only possible but ubiquitous among Lepidoptera.

A moving source of matrix components is essential for De Novo basement membrane formation - Matsubayashi, Yutaka; Louani, Adam; Dragu, Anca; Sanchez Sanchez, Besaiz; Serna Morales, Eduardo; Yolland, Lawrence; György, Attila; Vizcay, Gema; Fleck, Roland; Heddleston, John; Chew, Teng; Siekhaus, Daria E; et al. (Current Biology)
The basement membrane (BM) is a thin layer of extracellular matrix (ECM) beneath nearly all epithelial cell types that is critical for cellular and tissue function. It is composed of numerous components conserved among all bilaterians [1]; however, it is unknown how all of these components are generated and subsequently constructed to form a fully mature BM in the living animal. Although BM formation is thought to simply involve a process of self-assembly [2], this concept suffers from a number of logistical issues when considering its construction in vivo. First, incorporation of BM components appears to be hierarchical [3-5], yet it is unclear whether their production during embryogenesis must also be regulated in a temporal fashion. Second, many BM proteins are produced not only by the cells residing on the BM but also by surrounding cell types [6-9], and it is unclear how large, possibly insoluble protein complexes [10] are delivered into the matrix. Here we exploit our ability to live image and genetically dissect de novo BM formation during Drosophila development. This reveals that there is a temporal hierarchy of BM protein production that is essential for proper component incorporation. Furthermore, we show that BM components require secretion by migrating macrophages (hemocytes) during their developmental dispersal, which is critical for embryogenesis. Indeed, hemocyte migration is essential to deliver a subset of ECM components evenly throughout the embryo. This reveals that de novo BM construction requires a combination of both production and distribution logistics allowing for the timely delivery of core components.

Mechanical on chip microwave circulator - Barzanjeh, Shabir; Wulf, Matthias; Peruzzo, Matilda; Kalaee, Mahmoud; Dieterle, Paul; Painter, Oskar; Fink, Johannes M (Nature Communications)
Nonreciprocal circuit elements form an integral part of modern measurement and communication systems. Mathematically they require breaking of time-reversal symmetry, typically achieved using magnetic materials and more recently using the quantum Hall effect, parametric permittivity modulation or Josephson nonlinearities. Here we demonstrate an on-chip magnetic-free circulator based on reservoir-engineered electromechanic interactions. Directional circulation is achieved with controlled phase-sensitive interference of six distinct electro-mechanical signal conversion paths. The presented circulator is compact, its silicon-on-insulator platform is compatible with both superconducting qubits and silicon photonics, and its noise performance is close to the quantum limit. With a high dynamic range, a tunable bandwidth of up to 30 MHz and an in situ reconfigurability as beam splitter or wavelength converter, it could pave the way for superconducting qubit processors with multiplexed on-chip signal processing and readout.

The power of choice in priority scheduling - Alistarh, Dan-Adrian; Kopinsky, Justin; Li, Jerry; Nadiradze, Giorgi (Proceedings of the ACM Symposium on Principles of Distributed Computing)
Consider the following random process: we are given n queues, into which elements of increasing labels are inserted uniformly at random. To remove an element, we pick two queues at random, and remove the element of lower label (higher priority) among the two. The cost of a removal is the rank of the label removed, among labels still present in any of the queues, that is, the distance from the optimal choice at each step. Variants of this strategy are prevalent in state-of-the-art concurrent priority queue implementations. Nonetheless, it is not known whether such implementations provide any rank guarantees, even in a sequential model. We answer this question, showing that this strategy provides surprisingly strong guarantees: Although the single-choice process, where we always insert and remove from a single randomly chosen queue, has degrading cost, going to infinity as we increase the number of steps, in the two choice process, the expected rank of a removed element is O(n) while the expected worst-case cost is O(n log n). These bounds are tight, and hold irrespective of the number of steps for which we run the process. The argument is based on a new technical connection between "heavily loaded" balls-into-bins processes and priority scheduling. Our analytic results inspire a new concurrent priority queue implementation, which improves upon the state of the art in terms of practical performance.

Relative periodic orbits form the backbone of turbulent pipe flow - Budanur, Nazmi B; Short, Kimberly; Farazmand, Mohammad; Willis, Ashley; Cvitanović, Predrag (Journal of Fluid Mechanics)
The chaotic dynamics of low-dimensional systems, such as Lorenz or Rössler flows, is guided by the infinity of periodic orbits embedded in their strange attractors. Whether this is also the case for the infinite-dimensional dynamics of Navier–Stokes equations has long been speculated, and is a topic of ongoing study. Periodic and relative periodic solutions have been shown to be involved in transitions to turbulence. Their relevance to turbulent dynamics – specifically, whether periodic orbits play the same role in high-dimensional nonlinear systems like the Navier–Stokes equations as they do in lower-dimensional systems – is the focus of the present investigation. We perform here a detailed study of pipe flow relative periodic orbits with energies and mean dissipations close to turbulent values. We outline several approaches to reduction of the translational symmetry of the system. We study pipe flow in a minimal computational cell at Re=2500, and report a library of invariant solutions found with the aid of the method of slices. Detailed study of the unstable manifolds of a sample of these solutions is consistent with the picture that relative periodic orbits are embedded in the chaotic saddle and that they guide the turbulent dynamics.

Al transmon qubits on silicon on insulator for quantum device integration - Keller, Andrew J; Dieterle, Paul; Fang, Michael; Berger, Brett; Fink, Johannes M; Painter, Oskar (Applied Physics Letters)
We present the fabrication and characterization of an aluminum transmon qubit on a silicon-on-insulator substrate. Key to the qubit fabrication is the use of an anhydrous hydrofluoric vapor process which selectively removes the lossy silicon oxide buried underneath the silicon device layer. For a 5.6 GHz qubit measured dispersively by a 7.1 GHz resonator, we find T1 = 3.5 μs and T∗2 = 2.2 μs. This process in principle permits the co-fabrication of silicon photonic and mechanical elements, providing a route towards chip-scale integration of electro-opto-mechanical transducers for quantum networking of superconducting microwave quantum circuits. The additional processing steps are compatible with established fabrication techniques for aluminum transmon qubits on silicon.

On the existence of ordinary triangles - Fulek, Radoslav; Mojarrad, Hossein; Naszódi, Márton; Solymosi, József; Stich, Sebastian; Szedlák, May (Computational Geometry: Theory and Applications)
Let P be a finite point set in the plane. A cordinary triangle in P is a subset of P consisting of three non-collinear points such that each of the three lines determined by the three points contains at most c points of P . Motivated by a question of Erdös, and answering a question of de Zeeuw, we prove that there exists a constant c > 0such that P contains a c-ordinary triangle, provided that P is not contained in the union of two lines. Furthermore, the number of c-ordinary triangles in P is Ω(| P |).

C-planarity of embedded cyclic c-graphs - Fulek, Radoslav (Computational Geometry: Theory and Applications)
We show that c-planarity is solvable in quadratic time for flat clustered graphs with three clusters if the combinatorial embedding of the underlying graph is fixed. In simpler graph-theoretical terms our result can be viewed as follows. Given a graph G with the vertex set partitioned into three parts embedded on a 2-sphere, our algorithm decides if we can augment G by adding edges without creating an edge-crossing so that in the resulting spherical graph the vertices of each part induce a connected sub-graph. We proceed by a reduction to the problem of testing the existence of a perfect matching in planar bipartite graphs. We formulate our result in a slightly more general setting of cyclic clustered graphs, i.e., the simple graph obtained by contracting each cluster, where we disregard loops and multi-edges, is a cycle.

The number and distribution of AMPA receptor channels containing fast kinetic GluA3 and GluA4 subunits at auditory nerve synapses depend on the target cells - Rubio, María; Matsui, Ko; Fukazawa, Yugo; Kamasawa, Naomi; Harada, Harumi; Itakura, Makoto; Molnár, Elek; Abe, Manabu; Sakimura, Kenji; Shigemoto, Ryuichi (Brain Structure and Function)
The neurotransmitter receptor subtype, number, density, and distribution relative to the location of transmitter release sites are key determinants of signal transmission. AMPA-type ionotropic glutamate receptors (AMPARs) containing GluA3 and GluA4 subunits are prominently expressed in subsets of neurons capable of firing action potentials at high frequencies, such as auditory relay neurons. The auditory nerve (AN) forms glutamatergic synapses on two types of relay neurons, bushy cells (BCs) and fusiform cells (FCs) of the cochlear nucleus. AN-BC and AN-FC synapses have distinct kinetics; thus, we investigated whether the number, density, and localization of GluA3 and GluA4 subunits in these synapses are differentially organized using quantitative freeze-fracture replica immunogold labeling. We identify a positive correlation between the number of AMPARs and the size of AN-BC and AN-FC synapses. Both types of AN synapses have similar numbers of AMPARs; however, the AN-BC have a higher density of AMPARs than AN-FC synapses, because the AN-BC synapses are smaller. A higher number and density of GluA3 subunits are observed at AN-BC synapses, whereas a higher number and density of GluA4 subunits are observed at AN-FC synapses. The intrasynaptic distribution of immunogold labeling revealed that AMPAR subunits, particularly GluA3, are concentrated at the center of the AN-BC synapses. The central distribution of AMPARs is absent in GluA3-knockout mice, and gold particles are evenly distributed along the postsynaptic density. GluA4 gold labeling was homogenously distributed along both synapse types. Thus, GluA3 and GluA4 subunits are distributed at AN synapses in a target-cell-dependent manner.

The genetic encoded toolbox for electron microscopy and connectomics - Shigemoto, Ryuichi; Jösch, Maximilian A (WIREs Developmental Biology)
Developments in bioengineering and molecular biology have introduced a palette of genetically encoded probes for identification of specific cell populations in electron microscopy. These probes can be targeted to distinct cellular compartments, rendering them electron dense through a subsequent chemical reaction. These electron densities strongly increase the local contrast in samples prepared for electron microscopy, allowing three major advances in ultrastructural mapping of circuits: genetic identification of circuit components, targeted imaging of regions of interest and automated analysis of the tagged circuits. Together, the gains from these advances can decrease the time required for the analysis of targeted circuit motifs by over two orders of magnitude. These genetic encoded tags for electron microscopy promise to simplify the analysis of circuit motifs and become a central tool for structure‐function studies of synaptic connections in the brain. We review the current state‐of‐the‐art with an emphasis on connectomics, the quantitative analysis of neuronal structures and motifs.

Stability of a fermionic N+1 particle system with point interactions - Moser, Thomas; Seiringer, Robert (Communications in Mathematical Physics)
We prove that a system of N fermions interacting with an additional particle via point interactions is stable if the ratio of the mass of the additional particle to the one of the fermions is larger than some critical m*. The value of m* is independent of N and turns out to be less than 1. This fact has important implications for the stability of the unitary Fermi gas. We also characterize the domain of the Hamiltonian of this model, and establish the validity of the Tan relations for all wave functions in the domain.

A note on the validity of Bogoliubov correction to mean field dynamics - Nam, Phan; Napiórkowski, Marcin M (Journal de Mathématiques Pures et Appliquées)
We study the norm approximation to the Schrödinger dynamics of N bosons in with an interaction potential of the form . Assuming that in the initial state the particles outside of the condensate form a quasi-free state with finite kinetic energy, we show that in the large N limit, the fluctuations around the condensate can be effectively described using Bogoliubov approximation for all . The range of β is expected to be optimal for this large class of initial states.

A new topology on the universal path space - Virk, Ziga; Zastrow, Andreas (Topology and its Applications)
We generalize Brazas’ topology on the fundamental group to the whole universal path space X˜ i.e., to the set of homotopy classes of all based paths. We develop basic properties of the new notion and provide a complete comparison of the obtained topology with the established topologies, in particular with the Lasso topology and the CO topology, i.e., the topology that is induced by the compact-open topology. It turns out that the new topology is the finest topology contained in the CO topology, for which the action of the fundamental group on the universal path space is a continuous group action.

Convergence rate for spectral distribution of addition of random matrices - Bao, Zhigang; Erdös, László; Schnelli, Kevin (Advances in Mathematics)
Let A and B be two N by N deterministic Hermitian matrices and let U be an N by N Haar distributed unitary matrix. It is well known that the spectral distribution of the sum H = A + UBU∗ converges weakly to the free additive convolution of the spectral distributions of A and B, as N tends to infinity. We establish the optimal convergence rate in the bulk of the spectrum.

Fast hole tunneling times in germanium hut wires probed by single-shot reflectometry - Vukusic, Lada; Kukucka, Josip; Watzinger, Hannes; Katsaros, Georgios (Nano Letters)
Heavy holes confined in quantum dots are predicted to be promising candidates for the realization of spin qubits with long coherence times. Here we focus on such heavy-hole states confined in germanium hut wires. By tuning the growth density of the latter we can realize a T-like structure between two neighboring wires. Such a structure allows the realization of a charge sensor, which is electrostatically and tunnel coupled to a quantum dot, with charge-transfer signals as high as 0.3 e. By integrating the T-like structure into a radiofrequency reflectometry setup, single-shot measurements allowing the extraction of hole tunneling times are performed. The extracted tunneling times of less than 10 μs are attributed to the small effective mass of Ge heavy-hole states and pave the way toward projective spin readout measurements.

Ant queens increase their reproductive efforts after pathogen infection - Giehr, Julia; Grasse, Anna V; Cremer, Sylvia; Heinze, Jürgen; Schrempf, Alexandra (Royal Society Open Science)
Infections with potentially lethal pathogens may negatively affect an individual’s lifespan and decrease its reproductive value. The terminal investment hypothesis predicts that individuals faced with a reduced survival should invest more into reproduction instead of maintenance and growth. Several studies suggest that individuals are indeed able to estimate their body condition and to increase their reproductive effort with approaching death, while other studies gave ambiguous results. We investigate whether queens of a perennial social insect (ant) are able to boost their reproduction following infection with an obligate killing pathogen. Social insect queens are special with regard to reproduction and aging, as they outlive conspecific non-reproductive workers. Moreover, in the ant Cardiocondyla obscurior, fecundity increases with queen age. However, it remained unclear whether this reflects negative reproductive senescence or terminal investment in response to approaching death. Here, we test whether queens of C. obscurior react to infection with the entomopathogenic fungus Metarhizium brunneum by an increased egg-laying rate. We show that a fungal infection triggers a reinforced investment in reproduction in queens. This adjustment of the reproductive rate by ant queens is consistent with predictions of the terminal investment hypothesis and is reported for the first time in a social insect.

When does frequency-independent selection maintain genetic variation? - Novak, Sebastian; Barton, Nicholas H (Genetics)
Frequency-independent selection is generally considered as a force that acts to reduce the genetic variation in evolving populations, yet rigorous arguments for this idea are scarce. When selection fluctuates in time, it is unclear whether frequency-independent selection may maintain genetic polymorphism without invoking additional mechanisms. We show that constant frequency-independent selection with arbitrary epistasis on a well-mixed haploid population eliminates genetic variation if we assume linkage equilibrium between alleles. To this end, we introduce the notion of frequency-independent selection at the level of alleles, which is sufficient to prove our claim and contains the notion of frequency-independent selection on haploids. When selection and recombination are weak but of the same order, there may be strong linkage disequilibrium; numerical calculations show that stable equilibria are highly unlikely. Using the example of a diallelic two-locus model, we then demonstrate that frequency-independent selection that fluctuates in time can maintain stable polymorphism if linkage disequilibrium changes its sign periodically. We put our findings in the context of results from the existing literature and point out those scenarios in which the possible role of frequency-independent selection in maintaining genetic variation remains unclear.

Regulation of Drosophila hematopoietic sites by Activin-β from active sensory neurons - Makhijani, Kalpana; Alexander, Brandy; Rao, Deepti; Petraki, Sophia; Herboso, Leire; Kukar, Katelyn; Batool, Itrat; Wachner, Stephanie; Gold, Katrina; Wong, Corinna; O'Connor, Michael; Brückner, Katja (Nature Communications)
An outstanding question in animal development, tissue homeostasis and disease is how cell populations adapt to sensory inputs. During Drosophila larval development, hematopoietic sites are in direct contact with sensory neuron clusters of the peripheral nervous system (PNS), and blood cells (hemocytes) require the PNS for their survival and recruitment to these microenvironments, known as Hematopoietic Pockets. Here we report that Activin-β, a TGF-β family ligand, is expressed by sensory neurons of the PNS and regulates the proliferation and adhesion of hemocytes. These hemocyte responses depend on PNS activity, as shown by agonist treatment and transient silencing of sensory neurons. Activin-β has a key role in this regulation, which is apparent from reporter expression and mutant analyses. This mechanism of local sensory neurons controlling blood cell adaptation invites evolutionary parallels with vertebrate hematopoietic progenitors and the independent myeloid system of tissue macrophages, whose regulation by local microenvironments remain undefined.

Finding eigenvalues of self-maps with the Kronecker canonical form - Ethier, Marc; Jablonski, Grzegorz; Mrozek, Marian (Special Sessions in Applications of Computer Algebra)
Recent research has examined how to study the topological features of a continuous self-map by means of the persistence of the eigenspaces, for given eigenvalues, of the endomorphism induced in homology over a field. This raised the question of how to select dynamically significant eigenvalues. The present paper aims to answer this question, giving an algorithm that computes the persistence of eigenspaces for every eigenvalue simultaneously, also expressing said eigenspaces as direct sums of “finite” and “singular” subspaces.

A study of lagrangean decompositions and dual ascent solvers for graph matching - Swoboda, Paul; Rother, Carsten; Abu Alhaija, Carsten; Kainmueller, Dagmar; Savchynskyy, Bogdan
We study the quadratic assignment problem, in computer vision also known as graph matching. Two leading solvers for this problem optimize the Lagrange decomposition duals with sub-gradient and dual ascent (also known as message passing) updates. We explore this direction further and propose several additional Lagrangean relaxations of the graph matching problem along with corresponding algorithms, which are all based on a common dual ascent framework. Our extensive empirical evaluation gives several theoretical insights and suggests a new state-of-the-art anytime solver for the considered problem. Our improvement over state-of-the-art is particularly visible on a new dataset with large-scale sparse problem instances containing more than 500 graph nodes each.

A message passing algorithm for the minimum cost multicut problem - Swoboda, Paul; Andres, Bjoern
We propose a dual decomposition and linear program relaxation of the NP-hard minimum cost multicut problem. Unlike other polyhedral relaxations of the multicut polytope, it is amenable to efficient optimization by message passing. Like other polyhedral relaxations, it can be tightened efficiently by cutting planes. We define an algorithm that alternates between message passing and efficient separation of cycle- and odd-wheel inequalities. This algorithm is more efficient than state-of-the-art algorithms based on linear programming, including algorithms written in the framework of leading commercial software, as we show in experiments with large instances of the problem from applications in computer vision, biomedical image analysis and data mining.

A dual ascent framework for Lagrangean decomposition of combinatorial problems - Swoboda, Paul; Kuske, Jan; Savchynskyy, Bogdan
We propose a general dual ascent framework for Lagrangean decomposition of combinatorial problems. Although methods of this type have shown their efficiency for a number of problems, so far there was no general algorithm applicable to multiple problem types. In this work, we propose such a general algorithm. It depends on several parameters, which can be used to optimize its performance in each particular setting. We demonstrate efficacy of our method on graph matching and multicut problems, where it outperforms state-of-the-art solvers including those based on subgradient optimization and off-the-shelf linear programming solvers.

Decoding of position in the developing neural tube from antiparallel morphogen gradients - Zagórski, Marcin P; Tabata, Yoji; Brandenberg, Nathalie; Lutolf, Matthias; Tkacik, Gasper; Bollenbach, Tobias; Briscoe, James; Kicheva, Anna (Science)
Like many developing tissues, the vertebrate neural tube is patterned by antiparallel morphogen gradients. To understand how these inputs are interpreted, we measured morphogen signaling and target gene expression in mouse embryos and chick ex vivo assays. From these data, we derived and validated a characteristic decoding map that relates morphogen input to the positional identity of neural progenitors. Analysis of the observed responses indicates that the underlying interpretation strategy minimizes patterning errors in response to the joint input of noisy opposing gradients. We reverse-engineered a transcriptional network that provides a mechanistic basis for the observed cell fate decisions and accounts for the precision and dynamics of pattern formation. Together, our data link opposing gradient dynamics in a growing tissue to precise pattern formation.

Mosaic analysis with double markers reveals distinct sequential functions of Lgl1 in neural stem cells - Beattie, Robert J; Postiglione, Maria P; Burnett, Laura; Laukoter, Susanne; Streicher, Carmen; Pauler, Florian; Xiao, Guanxi; Klezovitch, Olga; Vasioukhin, Valeri; Ghashghaei, Troy; Hippenmeyer, Simon (Neuron)
The concerted production of neurons and glia by neural stem cells (NSCs) is essential for neural circuit assembly. In the developing cerebral cortex, radial glia progenitors (RGPs) generate nearly all neocortical neurons and certain glia lineages. RGP proliferation behavior shows a high degree of non-stochasticity, thus a deterministic characteristic of neuron and glia production. However, the cellular and molecular mechanisms controlling RGP behavior and proliferation dynamics in neurogenesis and glia generation remain unknown. By using mosaic analysis with double markers (MADM)-based genetic paradigms enabling the sparse and global knockout with unprecedented single-cell resolution, we identified Lgl1 as a critical regulatory component. We uncover Lgl1-dependent tissue-wide community effects required for embryonic cortical neurogenesis and novel cell-autonomous Lgl1 functions controlling RGP-mediated glia genesis and postnatal NSC behavior. These results suggest that NSC-mediated neuron and glia production is tightly regulated through the concerted interplay of sequential Lgl1-dependent global and cell intrinsic mechanisms.

S3: Syntax- and semantic-guided repair synthesis via programming by examples - Le, Xuan; Chu, Duc Hiep; Lo, David; Le Goues, Claire; Visser, Willem
A notable class of techniques for automatic program repair is known as semantics-based. Such techniques, e.g., Angelix, infer semantic specifications via symbolic execution, and then use program synthesis to construct new code that satisfies those inferred specifications. However, the obtained specifications are naturally incomplete, leaving the synthesis engine with a difficult task of synthesizing a general solution from a sparse space of many possible solutions that are consistent with the provided specifications but that do not necessarily generalize. We present S3, a new repair synthesis engine that leverages programming-by-examples methodology to synthesize high-quality bug repairs. The novelty in S3 that allows it to tackle the sparse search space to create more general repairs is three-fold: (1) A systematic way to customize and constrain the syntactic search space via a domain-specific language, (2) An efficient enumeration-based search strategy over the constrained search space, and (3) A number of ranking features based on measures of the syntactic and semantic distances between candidate solutions and the original buggy program. We compare S3’s repair effectiveness with state-of-the-art synthesis engines Angelix, Enumerative, and CVC4. S3 can successfully and correctly fix at least three times more bugs than the best baseline on datasets of 52 bugs in small programs, and 100 bugs in real-world large programs.

Waveguides with absorbing boundaries: Nonlinearity controlled by an exceptional point and solitons - Midya, Bikashkali; Konotop, Vladimir (Physical Review Letters)
We reveal the existence of continuous families of guided single-mode solitons in planar waveguides with weakly nonlinear active core and absorbing boundaries. Stable propagation of TE and TM-polarized solitons is accompanied by attenuation of all other modes, i.e., the waveguide features properties of conservative and dissipative systems. If the linear spectrum of the waveguide possesses exceptional points, which occurs in the case of TM polarization, an originally focusing (defocusing) material nonlinearity may become effectively defocusing (focusing). This occurs due to the geometric phase of the carried eigenmode when the surface impedance encircles the exceptional point. In its turn, the change of the effective nonlinearity ensures the existence of dark (bright) solitons in spite of focusing (defocusing) Kerr nonlinearity of the core. The existence of an exceptional point can also result in anomalous enhancement of the effective nonlinearity. In terms of practical applications, the nonlinearity of the reported waveguide can be manipulated by controlling the properties of the absorbing cladding.

Raw data from ant queens increase their reproductive efforts after pathogen infection - Giehr, Julia; Grasse, Anna V; Cremer, Sylvia; Heinze, Jürgen; Schrempf, Alexandra
Egg laying rates and infection loads of C. obscurior queens

Interaction networks, ecological stability, and collective antibiotic tolerance in polymicrobial infections - De Vos, Marjon; Zagórski, Marcin P; Mcnally, Alan; Bollenbach, Mark Tobias (PNAS)
Polymicrobial infections constitute small ecosystems that accommodate several bacterial species. Commonly, these bacteria are investigated in isolation. However, it is unknown to what extent the isolates interact and whether their interactions alter bacterial growth and ecosystem resilience in the presence and absence of antibiotics. We quantified the complete ecological interaction network for 72 bacterial isolates collected from 23 individuals diagnosed with polymicrobial urinary tract infections and found that most interactions cluster based on evolutionary relatedness. Statistical network analysis revealed that competitive and cooperative reciprocal interactions are enriched in the global network, while cooperative interactions are depleted in the individual host community networks. A population dynamics model parameterized by our measurements suggests that interactions restrict community stability, explaining the observed species diversity of these communities. We further show that the clinical isolates frequently protect each other from clinically relevant antibiotics. Together, these results highlight that ecological interactions are crucial for the growth and survival of bacteria in polymicrobial infection communities and affect their assembly and resilience.

Streaming algorithm for Euler characteristic curves of multidimensional images - Heiss, Teresa; Wagner, Hubert
We present an efficient algorithm to compute Euler characteristic curves of gray scale images of arbitrary dimension. In various applications the Euler characteristic curve is used as a descriptor of an image. Our algorithm is the first streaming algorithm for Euler characteristic curves. The usage of streaming removes the necessity to store the entire image in RAM. Experiments show that our implementation handles terabyte scale images on commodity hardware. Due to lock-free parallelism, it scales well with the number of processor cores. Additionally, we put the concept of the Euler characteristic curve in the wider context of computational topology. In particular, we explain the connection with persistence diagrams.

The E2A splice variant E47 regulates the differentiation of projection neurons via p57(KIP2) during cortical development - Pfurr, Sabrina; Chu, Yu; Bohrer, Christian; Greulich, Franziska; Beattie, Robert J; Mammadzada, Könül; Hils, Miriam; Arnold, Sebastian; Taylor, Verdon; Schachtrup, Kristina; Uhlenhaut, N Henriette; Schachtrup, Christian (Development)
During corticogenesis, distinct classes of neurons are born from progenitor cells located in the ventricular and subventricular zones, from where they migrate towards the pial surface to assemble into highly organized layer-specific circuits. However, the precise and coordinated transcriptional network activity defining neuronal identity is still not understood. Here, we show that genetic depletion of the basic helix-loop-helix (bHLH) transcription factor E2A splice variant E47 increased the number of Tbr1-positive deep layer and Satb2-positive upper layer neurons at E14.5, while depletion of the alternatively spliced E12 variant did not affect layer-specific neurogenesis. While ChIP-Seq identified a big overlap for E12- and E47-specific binding sites in embryonic NSCs, including sites at the cyclin-dependent kinase inhibitor (CDKI) Cdkn1c gene locus, RNA-Seq revealed a unique transcriptional regulation by each splice variant. E47 activated the expression of the CDKI Cdkn1c through binding to a distal enhancer. Finally, overexpression of E47 in embryonic NSCs in vitro impaired neurite outgrowth and E47 overexpression in vivo by in utero electroporation disturbed proper layer-specific neurogenesis and upregulated p57(KIP2) expression. Overall, this study identified E2A target genes in embryonic NSCs and demonstrates that E47 regulates neuronal differentiation via p57(KIP2).

Thouless energy and multifractality across the many-body localization transition - Serbyn, Maksym; Zlatko, Papic; Abanin, Dmitry (Physical Review B - Condensed Matter and Materials Physics)
Thermal and many-body localized phases are separated by a dynamical phase transition of a new kind. We analyze the distribution of off-diagonal matrix elements of local operators across this transition in two different models of disordered spin chains. We show that the behavior of matrix elements can be used to characterize the breakdown of thermalization and to extract the many-body Thouless energy. We find that upon increasing the disorder strength the system enters a critical region around the many-body localization transition. The properties of the system in this region are: (i) the Thouless energy becomes smaller than the level spacing, (ii) the matrix elements show critical dependence on the energy difference, and (iii) the matrix elements, viewed as amplitudes of a fictitious wave function, exhibit strong multifractality. This critical region decreases with the system size, which we interpret as evidence for a diverging correlation length at the many-body localization transition. Our findings show that the correlation length becomes larger than the accessible system sizes in a broad range of disorder strength values and shed light on the critical behavior near the many-body localization transition.

Phase transitions in integer linear problems - Colabrese, Simona; De Martino, Daniele; Leuzzi, Luca; Marinari, Enzo (Journal of Statistical Mechanics: Theory and Experiment)
The resolution of a linear system with positive integer variables is a basic yet difficult computational problem with many applications. We consider sparse uncorrelated random systems parametrised by the density c and the ratio α=N/M between number of variables N and number of constraints M. By means of ensemble calculations we show that the space of feasible solutions endows a Van-Der-Waals phase diagram in the plane (c, α). We give numerical evidence that the associated computational problems become more difficult across the critical point and in particular in the coexistence region.

Heteroclinic path to spatially localized chaos in pipe flow - Budanur, Nazmi B; Hof, Björn (Journal of Fluid Mechanics)
In shear flows at transitional Reynolds numbers, localized patches of turbulence, known as puffs, coexist with the laminar flow. Recently, Avila et al. (Phys. Rev. Lett., vol. 110, 2013, 224502) discovered two spatially localized relative periodic solutions for pipe flow, which appeared in a saddle-node bifurcation at low Reynolds number. Combining slicing methods for continuous symmetry reduction with Poincaré sections for the first time in a shear flow setting, we compute and visualize the unstable manifold of the lower-branch solution and show that it extends towards the neighbourhood of the upper-branch solution. Surprisingly, this connection even persists far above the bifurcation point and appears to mediate the first stage of the puff generation: amplification of streamwise localized fluctuations. When the state-space trajectories on the unstable manifold reach the vicinity of the upper branch, corresponding fluctuations expand in space and eventually take the usual shape of a puff.

BEN3/BIG2 ARF GEF is involved in brefeldin a-sensitive trafficking at the trans-Golgi network/early endosome in Arabidopsis thaliana - Kitakura, Saeko; Adamowski, Maciek; Matsuura, Yuki; Santuari, Luca; Kouno, Hirotaka; Arima, Kohei; Hardtke, Christian; Friml, Jirí; Kakimoto, Tatsuo; Tanaka, Hirokazu (Plant and Cell Physiology)
Membrane traffic at the trans-Golgi network (TGN) is crucial for correctly distributing various membrane proteins to their destination. Polarly localized auxin efflux proteins, including PIN-FORMED1 (PIN1), are dynamically transported between the endosomes and the plasma membrane (PM) in the plant cells. The intracellular trafficking of PIN1 protein is sensitive to a fungal toxin brefeldin A (BFA), which is known to inhibit guanine-nucleotide exchange factors for ADP ribosylation factors (ARF GEFs) such as GNOM. However, the molecular details of the BFA-sensitive trafficking pathway have not been revealed fully. In a previous study, we have identified an Arabidopsis mutant BFA-visualized endocytic trafficking defective 3 (ben3) which exhibited reduced sensitivity to BFA in terms of BFA-induced intracellular PIN1 agglomeration. Here, we show that BEN3 encodes a member of BIG family ARF GEFs, BIG2. Fluorescent proteins tagged BEN3/BIG2 co-localized with markers for TGN / early endosome (EE). Inspection of conditionally induced de novo synthesized PIN1 confirmed that its secretion to the PM is BFA-sensitive and established BEN3/BIG2 as a crucial component of this BFA action at the level of TGN/EE. Furthermore, ben3 mutation alleviated BFA-induced agglomeration of another TGN-localized ARF GEF BEN1/MIN7. Taken together our results suggest that BEN3/BIG2 is an ARF GEF component, which confers BFA sensitivity to the TGN/EE in Arabidopsis.

Distance-dependent inhibition facilitates focality of gamma oscillations in the dentate gyrus - Strüber, Michael; Sauer, Jonas; Jonas, Peter M; Bartos, Marlene (Nature Communications)
Gamma oscillations (30–150 Hz) in neuronal networks are associated with the processing and recall of information. We measured local field potentials in the dentate gyrus of freely moving mice and found that gamma activity occurs in bursts, which are highly heterogeneous in their spatial extensions, ranging from focal to global coherent events. Synaptic communication among perisomatic-inhibitory interneurons (PIIs) is thought to play an important role in the generation of hippocampal gamma patterns. However, how neuronal circuits can generate synchronous oscillations at different spatial scales is unknown. We analyzed paired recordings in dentate gyrus slices and show that synaptic signaling at interneuron-interneuron synapses is distance dependent. Synaptic strength declines whereas the duration of inhibitory signals increases with axonal distance among interconnected PIIs. Using neuronal network modeling, we show that distance-dependent inhibition generates multiple highly synchronous focal gamma bursts allowing the network to process complex inputs in parallel in flexibly organized neuronal centers.

DNA cross-bridging shapes a single nucleus from a set of mitotic chromosomes - Samwer, Matthias; Schneider, Maximilian; Hoefler, Rudolf; Schmalhorst, Philipp S; Jude, Julian; Zuber, Johannes; Gerlic, Daniel (Cell)
Eukaryotic cells store their chromosomes in a single nucleus. This is important to maintain genomic integrity, as chromosomes packaged into separate nuclei (micronuclei) are prone to massive DNA damage. During mitosis, higher eukaryotes disassemble their nucleus and release individualized chromosomes for segregation. How numerous chromosomes subsequently reform a single nucleus has remained unclear. Using image-based screening of human cells, we identified barrier-to-autointegration factor (BAF) as a key factor guiding membranes to form a single nucleus. Unexpectedly, nuclear assembly does not require BAF?s association with inner nuclear membrane proteins but instead relies on BAF?s ability to bridge distant DNA sites. Live-cell imaging and in vitro reconstitution showed that BAF enriches around the mitotic chromosome ensemble to induce a densely cross-bridged chromatin layer that is mechanically stiff and limits membranes to the surface. Our study reveals that BAF-mediated changes in chromosome mechanics underlie nuclear assembly with broad implications for proper genome function.

Overcoming the limitations of the MARTINI force field in simulations of polysaccharides - Schmalhorst, Philipp S; Deluweit, Felix; Scherrers, Roger; Heisenberg, Carl-Philipp J; Sikora, Mateusz K (Journal of Chemical Theory and Computation)
Polysaccharides (carbohydrates) are key regulators of a large number of cell biological processes. However, precise biochemical or genetic manipulation of these often complex structures is laborious and hampers experimental structure–function studies. Molecular Dynamics (MD) simulations provide a valuable alternative tool to generate and test hypotheses on saccharide function. Yet, currently used MD force fields often overestimate the aggregation propensity of polysaccharides, affecting the usability of those simulations. Here we tested MARTINI, a popular coarse-grained (CG) force field for biological macromolecules, for its ability to accurately represent molecular forces between saccharides. To this end, we calculated a thermodynamic solution property, the second virial coefficient of the osmotic pressure (B22). Comparison with light scattering experiments revealed a nonphysical aggregation of a prototypical polysaccharide in MARTINI, pointing at an imbalance of the nonbonded solute–solute, solute–water, and water–water interactions. This finding also applies to smaller oligosaccharides which were all found to aggregate in simulations even at moderate concentrations, well below their solubility limit. Finally, we explored the influence of the Lennard-Jones (LJ) interaction between saccharide molecules and propose a simple scaling of the LJ interaction strength that makes MARTINI more reliable for the simulation of saccharides.

Altered surface mGluR5 dynamics provoke synaptic NMDAR dysfunction and cognitive defects in Fmr1 knockout mice - Aloisi, Elisabetta; Le Corf, Katy; Dupuis, Julien; Zhang, Pei; Ginger, Melanie; Labrousse, Virginie; Spatuzza, Michela; Georg Haberl, Matthias; Costa, Lara; Shigemoto, Ryuichi; Tappe Theodor, Anke; Drago, Fillippo; et al. (Nature Communications)
Metabotropic glutamate receptor subtype 5 (mGluR5) is crucially implicated in the pathophysiology of Fragile X Syndrome (FXS); however, its dysfunction at the sub-cellular level, and related synaptic and cognitive phenotypes are unexplored. Here, we probed the consequences of mGluR5/Homer scaffold disruption for mGluR5 cell-surface mobility, synaptic N-methyl-D-Aspartate receptor (NMDAR) function, and behavioral phenotypes in the second-generation Fmr1 knockout (KO) mouse. Using single-molecule tracking, we found that mGluR5 was significantly more mobile at synapses in hippocampal Fmr1 KO neurons, causing an increased synaptic surface co-clustering of mGluR5 and NMDAR. This correlated with a reduced amplitude of synaptic NMDAR currents, a lack of their mGluR5-Activated long-Term depression, and NMDAR/hippocampus dependent cognitive deficits. These synaptic and behavioral phenomena were reversed by knocking down Homer1a in Fmr1 KO mice. Our study provides a mechanistic link between changes of mGluR5 dynamics and pathological phenotypes of FXS, unveiling novel targets for mGluR5-based therapeutics.

Triple function of Synaptotagmin 7 ensures efficiency of high-frequency transmission at central GABAergic synapses - Chen, Chong; Satterfield, Rachel; Young, Samuel; Jonas, Peter M (Cell Reports)
Synaptotagmin 7 (Syt7) is thought to be a Ca2+ sensor that mediates asynchronous transmitter release and facilitation at synapses. However, Syt7 is strongly expressed in fast-spiking, parvalbumin-expressing GABAergic interneurons, and the output synapses of these neurons produce only minimal asynchronous release and show depression rather than facilitation. To resolve this apparent contradiction, we examined the effects of genetic elimination of Syt7 on synaptic transmission at the GABAergic basket cell (BC)-Purkinje cell (PC) synapse in cerebellum. Our results indicate that at the BC-PC synapse, Syt7 contributes to asynchronous release, pool replenishment, and facilitation. In combination, these three effects ensure efficient transmitter release during high-frequency activity and guarantee frequency independence of inhibition. Our results identify a distinct function of Syt7: ensuring the efficiency of high-frequency inhibitory synaptic transmission

Optional interactions and suspicious behaviour facilitates trustful cooperation in prisoners dilemma - Priklopil, Tadeas; Chatterjee, Krishnendu; Nowak, Martin (Journal of Theoretical Biology)
In evolutionary game theory interactions between individuals are often assumed obligatory. However, in many real-life situations, individuals can decide to opt out of an interaction depending on the information they have about the opponent. We consider a simple evolutionary game theoretic model to study such a scenario, where at each encounter between two individuals the type of the opponent (cooperator/defector) is known with some probability, and where each individual either accepts or opts out of the interaction. If the type of the opponent is unknown, a trustful individual accepts the interaction, whereas a suspicious individual opts out of the interaction. If either of the two individuals opt out both individuals remain without an interaction. We show that in the prisoners dilemma optional interactions along with suspicious behaviour facilitates the emergence of trustful cooperation.

Transition to turbulence in pulsating pipe flow - Xu, Duo; Warnecke, Sascha; Song, Baofang; Ma, Xingyu; Hof, Björn (Journal of Fluid Mechanics)
Fluid flows in nature and applications are frequently subject to periodic velocity modulations. Surprisingly, even for the generic case of flow through a straight pipe, there is little consensus regarding the influence of pulsation on the transition threshold to turbulence: while most studies predict a monotonically increasing threshold with pulsation frequency (i.e. Womersley number, ), others observe a decreasing threshold for identical parameters and only observe an increasing threshold at low . In the present study we apply recent advances in the understanding of transition in steady shear flows to pulsating pipe flow. For moderate pulsation amplitudes we find that the first instability encountered is subcritical (i.e. requiring finite amplitude disturbances) and gives rise to localized patches of turbulence ('puffs') analogous to steady pipe flow. By monitoring the impact of pulsation on the lifetime of turbulence we map the onset of turbulence in parameter space. Transition in pulsatile flow can be separated into three regimes. At small Womersley numbers the dynamics is dominated by the decay turbulence suffers during the slower part of the cycle and hence transition is delayed significantly. As shown in this regime thresholds closely agree with estimates based on a quasi-steady flow assumption only taking puff decay rates into account. The transition point predicted in the zero limit equals to the critical point for steady pipe flow offset by the oscillation Reynolds number (i.e. the dimensionless oscillation amplitude). In the high frequency limit on the other hand, puff lifetimes are identical to those in steady pipe flow and hence the transition threshold appears to be unaffected by flow pulsation. In the intermediate frequency regime the transition threshold sharply drops (with increasing ) from the decay dominated (quasi-steady) threshold to the steady pipe flow level.

Modulation of cardiac vagal tone by bradykinin acting on nucleus ambiguus - Brǎiloiu, Eugen; Mcguire, Matthew; Shuler, Shadaria; Deliu, Elena; Barr, Jeffrey; Abood, Mary; Brailoiu, Gabriela (Neuroscience)
Bradykinin (BK), a component of the kallikrein-kininogen-kinin system exerts multiple effects via B1 and B2 receptor activation. In the cardiovascular system, bradykinin has cardioprotective and vasodilator properties. We investigated the effect of BK on cardiac-projecting neurons of nucleus ambiguus, a key site for the parasympathetic cardiac regulation. BK produced a dose-dependent increase in cytosolic Ca2+ concentration. Pretreatment with HOE140, a B2 receptor antagonist, but not with R715, a B1 receptor antagonist, abolished the response to BK. A selective B2 receptor agonist, but not a B1 receptor agonist, elicited an increase in cytosolic Ca2+ similarly to BK. Inhibition of N-type voltage-gated Ca2+ channels with ω-conotoxin GVIA had no effect on the Ca2+ signal produced by BK, while pretreatment with ω-conotoxin MVIIC, a blocker of P/Q-type of Ca2+ channels, significantly diminished the effect of BK. Pretreatment with xestospongin C and 2-aminoethoxydiphenyl borate, antagonists of inositol 1,4,5-trisphosphate receptors, abolished the response to BK. Inhibition of ryanodine receptors reduced the BK-induced Ca2+ increase, while disruption of lysosomal Ca2+ stores with bafilomycin A1 did not affect the response. BK produced a dose-dependent depolarization of nucleus ambiguus neurons, which was prevented by the B2 receptor antagonist. In vivo studies indicate that microinjection of BK into nucleus ambiguus elicited bradycardia in conscious rats via B2 receptors. In summary, in cardiac vagal neurons of nucleus ambiguus, BK activates B2 receptors promoting Ca2+ influx and Ca2+ release from endoplasmic reticulum, and membrane depolarization; these effects are translated in vivo by bradycardia.

Preface of the special issue in memoriam Helmut Veith - Gottlob, Georg; Henzinger, Thomas A; Weißenbacher, Georg (Formal Methods in System Design)
This special issue of the Journal on Formal Methods in System Design is dedicated to Prof. Helmut Veith, who unexpectedly passed away in March 2016. Helmut Veith was a brilliant researcher, inspiring collaborator, passionate mentor, generous friend, and valued member of the formal methods community. Helmut was not only known for his numerous and influential contributions in the field of automated verification (most prominently his work on Counterexample-Guided Abstraction Refinement [1,2]), but also for his untiring and passionate efforts for the logic community: he co-organized the Vienna Summer of Logic (an event comprising twelve conferences and numerous workshops which attracted thousands of researchers from all over the world), he initiated the Vienna Center for Logic and Algorithms (which promotes international collaboration on logic and algorithms and organizes outreach events such as the LogicLounge), and he coordinated the Doctoral Program on Logical Methods in Computer Science at TU Wien (currently educating more than 40 doctoral students) and a National Research Network on Rigorous Systems Engineering (uniting fifteen researchers in Austria to address the challenge of building reliable and safe computer systems). With his enthusiasm and commitment, Helmut completely reshaped the Austrian research landscape in the field of logic and verification in his few years as a full professor at TU Wien.

Cell adhesion and cell fate: An effective feedback loop during zebrafish gastrulation - Barone, Vanessa
Cell-cell contact formation constitutes the first step in the emergence of multicellularity in evolution, thereby allowing the differentiation of specialized cell types. In metazoan development, cell-cell contact formation is thought to influence cell fate specification, and cell fate specification has been implicated in cell-cell contact formation. However, remarkably little is yet known about whether and how the interaction and feedback between cell-cell contact formation and cell fate specification affect development. Here we identify a positive feedback loop between cell-cell contact duration, morphogen signaling and mesendoderm cell fate specification during zebrafish gastrulation. We show that long lasting cell-cell contacts enhance the competence of prechordal plate (ppl) progenitor cells to respond to Nodal signaling, required for proper ppl cell fate specification. We further show that Nodal signalling romotes ppl cell-cell contact duration, thereby generating an effective positive feedback loop between ppl cell-cell contact duration and cell fate specification. Finally, by using a combination of theoretical modeling and experimentation, we show that this feedback loop determines whether anterior axial mesendoderm cells become ppl progenitors or, instead, turn into endoderm progenitors. Our findings reveal that the gene regulatory networks leading to cell fate diversification within the developing embryo are controlled by the interdependent activities of cell-cell signaling and contact formation.

Deconstructing superorganisms and societies to address big questions in biology - Kennedy, Patrick; Baron, Gemma; Qiu, Bitao; Freitak, Dalial; Helantera, Heikki; Hunt, Edmund; Manfredini, Fabio; O'Shea Wheller, Thomas; Patalano, Solenn; Pull, Christopher; Sasaki, Takao; Taylor, Daisy; et al. (Trends in Ecology and Evolution)
Social insect societies are long-standing models for understanding social behaviour and evolution. Unlike other advanced biological societies (such as the multicellular body), the component parts of social insect societies can be easily deconstructed and manipulated. Recent methodological and theoretical innovations have exploited this trait to address an expanded range of biological questions. We illustrate the broadening range of biological insight coming from social insect biology with four examples. These new frontiers promote open-minded, interdisciplinary exploration of one of the richest and most complex of biological phenomena: sociality.

Disease defence in garden ants - Pull, Christopher
Contagious diseases must transmit from infectious to susceptible hosts in order to reproduce. Whilst vectored pathogens can rely on intermediaries to find new hosts for them, many infectious pathogens require close contact or direct interaction between hosts for transmission. Hence, this means that conspecifics are often the main source of infection for most animals and so, in theory, animals should avoid conspecifics to reduce their risk of infection. Of course, in reality animals must interact with one another, as a bare minimum, to mate. However, being social provides many additional benefits and group living has become a taxonomically diverse and widespread trait. How then do social animals overcome the issue of increased disease? Over the last few decades, the social insects (ants, termites and some bees and wasps) have become a model system for studying disease in social animals. On paper, a social insect colony should be particularly susceptible to disease, given that they often contain thousands of potential hosts that are closely related and frequently interact, as well as exhibiting stable environmental conditions that encourage microbial growth. Yet, disease outbreaks appear to be rare and attempts to eradicate pest species using pathogens have failed time and again. Evolutionary biologists investigating this observation have discovered that the reduced disease susceptibility in social insects is, in part, due to collectively performed disease defences of the workers. These defences act like a “social immune system” for the colony, resulting in a per capita decrease in disease, termed social immunity. Our understanding of social immunity, and its importance in relation to the immunological defences of each insect, continues to grow, but there remain many open questions. In this thesis I have studied disease defence in garden ants. In the first data chapter, I use the invasive garden ant, Lasius neglectus, to investigate how colonies mitigate lethal infections and prevent them from spreading systemically. I find that ants have evolved ‘destructive disinfection’ – a behaviour that uses endogenously produced acidic poison to kill diseased brood and to prevent the pathogen from replicating. In the second experimental chapter, I continue to study the use of poison in invasive garden ant colonies, finding that it is sprayed prophylactically within the nest. However, this spraying has negative effects on developing pupae when they have had their cocoons artificially removed. Hence, I suggest that acidic nest sanitation may be maintaining larval cocoon spinning in this species. In the next experimental chapter, I investigated how colony founding black garden ant queens (Lasius niger) prevent disease when a co-foundress dies. I show that ant queens prophylactically perform undertaking behaviours, similar to those performed by the workers in mature nests. When a co-foundress was infected, these undertaking behaviours improved the survival of the healthy queen. In the final data chapter, I explored how immunocompetence (measured as antifungal activity) changes as incipient black garden ant colonies grow and mature, from the solitary queen phase to colonies with several hundred workers. Queen and worker antifungal activity varied throughout this time period, but despite social immunity, did not decrease as colonies matured. In addition to the above data chapters, this thesis includes two co-authored reviews. In the first, we examine the state of the art in the field of social immunity and how it might develop in the future. In the second, we identify several challenges and open questions in the study of disease defence in animals. We highlight how social insects offer a unique model to tackle some of these problems, as disease defence can be studied from the cell to the society.

Co-founding ant queens prevent disease by performing prophylactic undertaking behaviour - Pull, Christopher; Cremer, Sylvia (BMC Evolutionary Biology)
Background: Social insects form densely crowded societies in environments with high pathogen loads, but have evolved collective defences that mitigate the impact of disease. However, colony-founding queens lack this protection and suffer high rates of mortality. The impact of pathogens may be exacerbated in species where queens found colonies together, as healthy individuals may contract pathogens from infectious co-founders. Therefore, we tested whether ant queens avoid founding colonies with pathogen-exposed conspecifics and how they might limit disease transmission from infectious individuals. Results: Using Lasius Niger queens and a naturally infecting fungal pathogen Metarhizium brunneum, we observed that queens were equally likely to found colonies with another pathogen-exposed or sham-treated queen. However, when one queen died, the surviving individual performed biting, burial and removal of the corpse. These undertaking behaviours were performed prophylactically, i.e. targeted equally towards non-infected and infected corpses, as well as carried out before infected corpses became infectious. Biting and burial reduced the risk of the queens contracting and dying from disease from an infectious corpse of a dead co-foundress. Conclusions: We show that co-founding ant queens express undertaking behaviours that, in mature colonies, are performed exclusively by workers. Such infection avoidance behaviours act before the queens can contract the disease and will therefore improve the overall chance of colony founding success in ant queens.

A unifying theory of branching morphogenesis - Hannezo, Edouard B; Scheele, Colinda; Moad, Mohammad; Drogo, Nicholas; Heer, Rakesh; Sampogna, Rosemary; Van Rheenen, Jacco; Simons, Benjamin (Cell)
The morphogenesis of branched organs remains a subject of abiding interest. Although much is known about the underlying signaling pathways, it remains unclear how macroscopic features of branched organs, including their size, network topology, and spatial patterning, are encoded. Here, we show that, in mouse mammary gland, kidney, and human prostate, these features can be explained quantitatively within a single unifying framework of branching and annihilating random walks. Based on quantitative analyses of large-scale organ reconstructions and proliferation kinetics measurements, we propose that morphogenesis follows from the proliferative activity of equipotent tips that stochastically branch and randomly explore their environment but compete neutrally for space, becoming proliferatively inactive when in proximity with neighboring ducts. These results show that complex branched epithelial structures develop as a self-organized process, reliant upon a strikingly simple but generic rule, without recourse to a rigid and deterministic sequence of genetically programmed events.

Load adaptation of lamellipodial actin networks - Mueller, Jan; Szep, Gregory; Nemethova, Maria; De Vries, Ingrid; Lieber, Arnon; Winkler, Christoph; Kruse, Karsten; Small, John; Schmeiser, Christian; Keren, Kinneret; Hauschild, Robert; Sixt, Michael K (Cell)
Actin filaments polymerizing against membranes power endocytosis, vesicular traffic, and cell motility. In vitro reconstitution studies suggest that the structure and the dynamics of actin networks respond to mechanical forces. We demonstrate that lamellipodial actin of migrating cells responds to mechanical load when membrane tension is modulated. In a steady state, migrating cell filaments assume the canonical dendritic geometry, defined by Arp2/3-generated 70° branch points. Increased tension triggers a dense network with a broadened range of angles, whereas decreased tension causes a shift to a sparse configuration dominated by filaments growing perpendicularly to the plasma membrane. We show that these responses emerge from the geometry of branched actin: when load per filament decreases, elongation speed increases and perpendicular filaments gradually outcompete others because they polymerize the shortest distance to the membrane, where they are protected from capping. This network-intrinsic geometrical adaptation mechanism tunes protrusive force in response to mechanical load.

Maximum entropy models as a tool for building precise neural controls - Savin, Cristina; Tkacik, Gasper (Current Opinion in Neurobiology)
Neural responses are highly structured, with population activity restricted to a small subset of the astronomical range of possible activity patterns. Characterizing these statistical regularities is important for understanding circuit computation, but challenging in practice. Here we review recent approaches based on the maximum entropy principle used for quantifying collective behavior in neural activity. We highlight recent models that capture population-level statistics of neural data, yielding insights into the organization of the neural code and its biological substrate. Furthermore, the MaxEnt framework provides a general recipe for constructing surrogate ensembles that preserve aspects of the data, but are otherwise maximally unstructured. This idea can be used to generate a hierarchy of controls against which rigorous statistical tests are possible.

Coordination of morphogenesis and cell fate specification in development - Chan, Chii; Heisenberg, Carl-Philipp J; Hiiragi, Takashi (Current Biology)
During animal development, cell-fate-specific changes in gene expression can modify the material properties of a tissue and drive tissue morphogenesis. While mechanistic insights into the genetic control of tissue-shaping events are beginning to emerge, how tissue morphogenesis and mechanics can reciprocally impact cell-fate specification remains relatively unexplored. Here we review recent findings reporting how multicellular morphogenetic events and their underlying mechanical forces can feed back into gene regulatory pathways to specify cell fate. We further discuss emerging techniques that allow for the direct measurement and manipulation of mechanical signals in vivo, offering unprecedented access to study mechanotransduction during development. Examination of the mechanical control of cell fate during tissue morphogenesis will pave the way to an integrated understanding of the design principles that underlie robust tissue patterning in embryonic development.

Regeneration tensed up polyploidy takes the lead - Spiro, Zoltan P; Heisenberg, Carl-Philipp J (Developmental Cell)
The cellular mechanisms allowing tissues to efficiently regenerate are not fully understood. In this issue of Developmental Cell, Cao et al. (2017)) discover that during zebrafish heart regeneration, epicardial cells at the leading edge of regenerating tissue undergo endoreplication, possibly due to increased tissue tension, thereby boosting their regenerative capacity.

Maximum entropy modeling of metabolic networks by constraining growth-rate moments predicts coexistence of phenotypes - De Martino, Daniele (Physical Review E)
In this work maximum entropy distributions in the space of steady states of metabolic networks are considered upon constraining the first and second moments of the growth rate. Coexistence of fast and slow phenotypes, with bimodal flux distributions, emerges upon considering control on the average growth (optimization) and its fluctuations (heterogeneity). This is applied to the carbon catabolic core of Escherichia coli where it quantifies the metabolic activity of slow growing phenotypes and it provides a quantitative map with metabolic fluxes, opening the possibility to detect coexistence from flux data. A preliminary analysis on data for E. coli cultures in standard conditions shows degeneracy for the inferred parameters that extend in the coexistence region.

Wave propagation reversal for wavy vortices in wide gap counter rotating cylindrical Couette flow - Altmeyer, Sebastian; Lueptow, Richard (Physical Review E)
We present a numerical study of wavy supercritical cylindrical Couette flow between counter-rotating cylinders in which the wavy pattern propagates either prograde with the inner cylinder or retrograde opposite the rotation of the inner cylinder. The wave propagation reversals from prograde to retrograde and vice versa occur at distinct values of the inner cylinder Reynolds number when the associated frequency of the wavy instability vanishes. The reversal occurs for both twofold and threefold symmetric wavy vortices. Moreover, the wave propagation reversal only occurs for sufficiently strong counter-rotation. The flow pattern reversal appears to be intrinsic in the system as either periodic boundary conditions or fixed end wall boundary conditions for different system sizes always result in the wave propagation reversal. We present a detailed bifurcation sequence and parameter space diagram with respect to retrograde behavior of wavy flows. The retrograde propagation of the instability occurs when the inner Reynolds number is about two times the outer Reynolds number. The mechanism for the retrograde propagation is associated with the inviscidly unstable region near the inner cylinder and the direction of the global average azimuthal velocity. Flow dynamics, spatio-temporal behavior, global mean angular velocity, and torque of the flow with the wavy pattern are explored.

Fluctuations of the competition interface in presence of shocks - Ferrari, Patrik; Nejjar, Peter (Revista Latino-Americana de Probabilidade e Estatística)
We consider last passage percolation (LPP) models with exponentially distributed random variables, which are linked to the totally asymmetric simple exclusion process (TASEP). The competition interface for LPP was introduced and studied in Ferrari and Pimentel (2005a) for cases where the corresponding exclusion process had a rarefaction fan. Here we consider situations with a shock and determine the law of the fluctuations of the competition interface around its deter- ministic law of large number position. We also study the multipoint distribution of the LPP around the shock, extending our one-point result of Ferrari and Nejjar (2015).

AAV2 mediated transduction of the mouse retina after optic nerve injury - Nickells, Robert; Schmitt, Heather; Maes, Margaret E; Schlamp, Cassandra (Investigative Ophthalmology and Visual Science)
PURPOSE. Gene therapy of retinal ganglion cells (RGCs) has promise as a powerful therapeutic for the rescue and regeneration of these cells after optic nerve damage. However, early after damage, RGCs undergo atrophic changes, including gene silencing. It is not known if these changes will deleteriously affect transduction and transgene expression, or if the therapeutic protein can influence reactivation of the endogenous genome. METHODS. Double-transgenic mice carrying a Rosa26-(LoxP)-tdTomato reporter, and a mutant allele for the proapoptotic Bax gene were reared. The Bax mutant blocks apoptosis, but RGCs still exhibit nuclear atrophy and gene silencing. At times ranging from 1 hour to 4 weeks after optic nerve crush (ONC), eyes received an intravitreal injection of AAV2 virus carrying the Cre recombinase. Successful transduction was monitored by expression of the tdTomato reporter. Immunostaining was used to localize tdTomato expression in select cell types. RESULTS. Successful transduction of RGCs was achieved at all time points after ONC using AAV2 expressing Cre from the phosphoglycerate kinase (Pgk) promoter, but not the CMV promoter. ONC promoted an increase in the transduction of cell types in the inner nuclear layer, including Müller cells and rod bipolar neurons. There was minimal evidence of transduction of amacrine cells and astrocytes in the inner retina or optic nerve. CONCLUSIONS. Damaged RGCs can be transduced and at least some endogenous genes can be subsequently activated. Optic nerve damage may change retinal architecture to allow greater penetration of an AAV2 virus to transduce several additional cell types in the inner nuclear layer.

Emergence of non-abelian magnetic monopoles in a quantum impurity problem - Yakaboylu, Enderalp; Deuchert, Andreas; Lemeshko, Mikhail (Physical Review Letters)
Recently it was shown that molecules rotating in superfluid helium can be described in terms of the angulon quasiparticles (Phys. Rev. Lett. 118, 095301 (2017)). Here we demonstrate that in the experimentally realized regime the angulon can be seen as a point charge on a 2-sphere interacting with a gauge field of a non-abelian magnetic monopole. Unlike in several other settings, the gauge fields of the angulon problem emerge in the real coordinate space, as opposed to the momentum space or some effective parameter space. Furthermore, we find a topological transition associated with making the monopole abelian, which takes place in the vicinity of the previously reported angulon instabilities. These results pave the way for studying topological phenomena in experiments on molecules trapped in superfluid helium nanodroplets, as well as on other realizations of orbital impurity problems.

Probabilistic image colorization - Royer, Amélie; Kolesnikov, Alexander; Lampert, Christoph
We develop a probabilistic technique for colorizing grayscale natural images. In light of the intrinsic uncertainty of this task, the proposed probabilistic framework has numerous desirable properties. In particular, our model is able to produce multiple plausible and vivid colorizations for a given grayscale image and is one of the first colorization models to provide a proper stochastic sampling scheme. Moreover, our training procedure is supported by a rigorous theoretical framework that does not require any ad hoc heuristics and allows for efficient modeling and learning of the joint pixel color distribution.We demonstrate strong quantitative and qualitative experimental results on the CIFAR-10 dataset and the challenging ILSVRC 2012 dataset.

Comparison of the effects of nicotinic acid and nicotinamide degradation on plasma betaine and choline levels - Sun, Wuping; Zhai, Ming-Zhu; Li, Da; Zhou, Yiming; Chen, Nana; Guo, Ming; Zhou, Shisheng (Clinical Nutrition)
Aim: The present study was to compare the effects of nicotinic acid and nicotinamide on the plasma methyl donors, choline and betaine. Methods: Thirty adult subjects were randomly divided into three groups of equal size, and orally received purified water (C group), nicotinic acid (300 mg, NA group) or nicotinamide (300 mg, NM group). Plasma nicotinamide, N 1-methylnicotinamide, homocysteine, betaine and choline levels before and 1.5-h and 3-h post-dosing, plasma normetanephrine and metanephrine concentrations at 3-h post-dosing, and the urinary excretion of N 1-methyl-2-pyridone-5-carboxamide during the test period were examined. Results: The level of 3-h plasma nicotinamide, N 1-methylnicotinamide, homocysteine, the urinary excretion of N 1-methyl-2-pyridone-5-carboxamide and pulse pressure (PP) in the NM group was 221%, 3972%, 61%, 1728% and 21.2% higher than that of the control group (P < 0.01, except homocysteine and PP P < 0.05), while the 3-h plasma betaine, normetanephrine and metanephrine level in the NM group was 24.4%, 9.4% and 11.7% lower (P < 0.05, except betaine P < 0.01), without significant difference in choline levels. Similar but less pronounced changes were observed in the NA group, with a lower level of 3-h plasma N 1-methylnicotinamide (1.90 ± 0.20 μmol/l vs. 3.62 ± 0.27 μmol/l, P < 0.01) and homocysteine (12.85 ± 1.39 μmol/l vs. 18.08 ± 1.02 μmol/l, P < 0.05) but a higher level of betaine (27.44 ± 0.71 μmol/l vs. 23.52 ± 0.61 μmol/l, P < 0.05) than that of the NM group. Conclusion: The degradation of nicotinamide consumes more betaine than that of nicotinic acid at identical doses. This difference should be taken into consideration in niacin fortification. © 2016 Elsevier Ltd and European Society for Clinical Nutrition and Metabolism.

Computational topology for structural molecular biology - Edelsbrunner, Herbert; Koehl, Patrice (Handbook of Discrete and Computational Geometry, Third Edition)
The advent of high-throughput technologies and the concurrent advances in information sciences have led to a data revolution in biology. This revolution is most significant in molecular biology, with an increase in the number and scale of the “omics” projects over the last decade. Genomics projects, for example, have produced impressive advances in our knowledge of the information concealed into genomes, from the many genes that encode for the proteins that are responsible for most if not all cellular functions, to the noncoding regions that are now known to provide regulatory functions. Proteomics initiatives help to decipher the role of post-translation modifications on the protein structures and provide maps of protein-protein interactions, while functional genomics is the field that attempts to make use of the data produced by these projects to understand protein functions. The biggest challenge today is to assimilate the wealth of information provided by these initiatives into a conceptual framework that will help us decipher life. For example, the current views of the relationship between protein structure and function remain fragmented. We know of their sequences, more and more about their structures, we have information on their biological activities, but we have difficulties connecting this dotted line into an informed whole. We lack the experimental and computational tools for directly studying protein structure, function, and dynamics at the molecular and supra-molecular levels. In this chapter, we review some of the current developments in building the computational tools that are needed, focusing on the role that geometry and topology play in these efforts. One of our goals is to raise the general awareness about the importance of geometric methods in elucidating the mysterious foundations of our very existence. Another goal is the broadening of what we consider a geometric algorithm. There is plenty of valuable no-man’s-land between combinatorial and numerical algorithms, and it seems opportune to explore this land with a computational-geometric frame of mind.

Dietary menthol-induced TRPM8 activation enhances WAT “browning” and ameliorates diet-induced obesity - Jiang, Changyu; Zhai, Ming-Zhu; Yan, Dong; Li, Da; Li, Chen; Zhang, Yonghong; Xiao, Lizu; Xiong, Donglin; Deng, Qiwen; Sun, Wuping (Oncotarget)
Beige adipocytes are a new type of recruitable brownish adipocytes, with highly mitochondrial membrane uncoupling protein 1 expression and thermogenesis. Beige adipocytes were found among white adipocytes, especially in subcutaneous white adipose tissue (sWAT). Therefore, beige adipocytes may be involved in the regulation of energy metabolism and fat deposition. Transient receptor potential melastatin 8 (TRPM8), a Ca2+-permeable non-selective cation channel, plays vital roles in the regulation of various cellular functions. It has been reported that TRPM8 activation enhanced the thermogenic function of brown adiposytes. However, the involvement of TRPM8 in the thermogenic function of WAT remains unexplored. Our data revealed that TRPM8 was expressed in mouse white adipocytes at mRNA, protein and functional levels. The mRNA expression of Trpm8 was significantly increased in the differentiated white adipocytes than pre-adipocytes. Moreover, activation of TRPM8 by menthol enhanced the expression of thermogenic genes in cultured white aidpocytes. And menthol-induced increases of the thermogenic genes in white adipocytes was inhibited by either KT5720 (a protein kinase A inhibitor) or BAPTA-AM. In addition, high fat diet (HFD)-induced obesity in mice was significantly recovered by co-treatment with menthol. Dietary menthol enhanced WAT "browning" and improved glucose metabolism in HFD-induced obesity mice as well. Therefore, we concluded that TRPM8 might be involved in WAT "browning" by increasing the expression levels of genes related to thermogenesis and energy metabolism. And dietary menthol could be a novel approach for combating human obesity and related metabolic diseases.

Zeros of nonlinear systems with input invariances - Lang, Moritz; Sontag, Eduardo (Automatica)
A nonlinear system possesses an invariance with respect to a set of transformations if its output dynamics remain invariant when transforming the input, and adjusting the initial condition accordingly. Most research has focused on invariances with respect to time-independent pointwise transformations like translational-invariance (u(t) -> u(t) + p, p in R) or scale-invariance (u(t) -> pu(t), p in R>0). In this article, we introduce the concept of s0-invariances with respect to continuous input transformations exponentially growing/decaying over time. We show that s0-invariant systems not only encompass linear time-invariant (LTI) systems with transfer functions having an irreducible zero at s0 in R, but also that the input/output relationship of nonlinear s0-invariant systems possesses properties well known from their linear counterparts. Furthermore, we extend the concept of s0-invariances to second- and higher-order s0-invariances, corresponding to invariances with respect to transformations of the time-derivatives of the input, and encompassing LTI systems with zeros of multiplicity two or higher. Finally, we show that nth-order 0-invariant systems realize – under mild conditions – nth-order nonlinear differential operators: when excited by an input of a characteristic functional form, the system’s output converges to a constant value only depending on the nth (nonlinear) derivative of the input.

Learning theory for conditional risk minimization - Zimin, Alexander; Lampert, Christoph
In this work we study the learnability of stochastic processes with respect to the conditional risk, i.e. the existence of a learning algorithm that improves its next-step performance with the amount of observed data. We introduce a notion of pairwise discrepancy between conditional distributions at different times steps and show how certain properties of these discrepancies can be used to construct a successful learning algorithm. Our main results are two theorems that establish criteria for learnability for many classes of stochastic processes, including all special cases studied previously in the literature.

On the lengths of curves passing through boundary points of a planar convex shape - Akopyan, Arseniy; Vysotsky, Vladislav (The American Mathematical Monthly)
We study the lengths of curves passing through a fixed number of points on the boundary of a convex shape in the plane. We show that, for any convex shape K, there exist four points on the boundary of K such that the length of any curve passing through these points is at least half of the perimeter of K. It is also shown that the same statement does not remain valid with the additional constraint that the points are extreme points of K. Moreover, the factor ½ cannot be achieved with any fixed number of extreme points. We conclude the paper with a few other inequalities related to the perimeter of a convex shape.

QSGD: Communication-efficient SGD via gradient quantization and encoding - Alistarh, Dan-Adrian; Grubic, Demjan; Li, Jerry; Tomioka, Ryota; Vojnović, Milan
Parallel implementations of stochastic gradient descent (SGD) have received significant research attention, thanks to its excellent scalability properties. A fundamental barrier when parallelizing SGD is the high bandwidth cost of communicating gradient updates between nodes; consequently, several lossy compresion heuristics have been proposed, by which nodes only communicate quantized gradients. Although effective in practice, these heuristics do not always converge. In this paper, we propose Quantized SGD (QSGD), a family of compression schemes with convergence guarantees and good practical performance. QSGD allows the user to smoothly trade off communication bandwidth and convergence time: nodes can adjust the number of bits sent per iteration, at the cost of possibly higher variance. We show that this trade-off is inherent, in the sense that improving it past some threshold would violate information-theoretic lower bounds. QSGD guarantees convergence for convex and non-convex objectives, under asynchrony, and can be extended to stochastic variance-reduced techniques. When applied to training deep neural networks for image classification and automated speech recognition, QSGD leads to significant reductions in end-to-end training time. For instance, on 16GPUs, we can train the ResNet-152 network to full accuracy on ImageNet 1.8 × faster than the full-precision variant.

Causality-based model checking - Finkbeiner, Bernd; Kupriyanov, Andrey (Electronic Proceedings in Theoretical Computer Science)
Model checking is usually based on a comprehensive traversal of the state space. Causality-based model checking is a radically different approach that instead analyzes the cause-effect relationships in a program. We give an overview on a new class of model checking algorithms that capture the causal relationships in a special data structure called concurrent traces. Concurrent traces identify key events in an execution history and link them through their cause-effect relationships. The model checker builds a tableau of concurrent traces, where the case splits represent different causal explanations of a hypothetical error. Causality-based model checking has been implemented in the ARCTOR tool, and applied to previously intractable multi-threaded benchmarks.

Multi-task learning with labeled and unlabeled tasks - Pentina, Anastasia; Lampert, Christoph
In multi-task learning, a learner is given a collection of prediction tasks and needs to solve all of them. In contrast to previous work, which required that annotated training data must be available for all tasks, we consider a new setting, in which for some tasks, potentially most of them, only unlabeled training data is provided. Consequently, to solve all tasks, information must be transferred between tasks with labels and tasks without labels. Focusing on an instance-based transfer method we analyze two variants of this setting: when the set of labeled tasks is fixed, and when it can be actively selected by the learner. We state and prove a generalization bound that covers both scenarios and derive from it an algorithm for making the choice of labeled tasks (in the active case) and for transferring information between the tasks in a principled way. We also illustrate the effectiveness of the algorithm on synthetic and real data.